Bilayer polyelectrolyte membrane

By adopting a double-layer polyelectrolyte membrane structure in a proton exchange membrane fuel cell, the cross-linked polysulfonated polymer layer is used to reduce hydrogen permeation, and the problems of reduced fuel efficiency and membrane damage caused by hydrogen permeation are solved, thereby achieving more efficient and safer fuel cell performance.

CN119547232APending Publication Date: 2025-02-28CELADYNE TECH INC
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202380046496.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-27
Filing Date
2023-04-14
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the existing proton exchange membrane fuel cell (PEMFC), the permeation of hydrogen leads to a decrease in fuel efficiency, a decrease in cathode potential and the formation of peroxide radicals, which in turn damages the membrane and catalyst layer.

Method used

A double-layer polyelectrolyte membrane structure is adopted, in which the first layer is perfluorosulfonic acid (PFSA) and the second layer is a crosslinked polysulfonated polymer, including sulfonated polyphenylsulfone (sPPS), sulfonated polyether ether ketone (sPEEK), etc., to reduce the permeation of hydrogen through crosslinking reaction.

Benefits of technology

It effectively reduces the penetration of hydrogen, extends the durability of the membrane and the service life of the fuel cell, and improves the efficiency and safety of the fuel cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119547232A_ABST
    Figure CN119547232A_ABST
Patent Text Reader

Abstract

The present disclosure relates to a bilayer polyelectrolyte membrane comprising a first layer and a second layer wherein the first layer comprises a perfluorosulfonic acid and the second layer comprises a cross-linked polysulfonated polymer, and wherein the first layer is disposed on the second layer. The present disclosure also relates to a method of manufacturing the bilayer polyelectrolyte membrane, and a membrane electrode assembly and a fuel cell comprising the bilayer polyelectrolyte membrane.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related Applications

[0002] This application claims the benefit of U.S. Provisional Application No. 63 / 331,007, filed April 14, 2022, U.S. Provisional Application No. 63 / 433,574, filed December 19, 2022, U.S. Provisional Application No. 63 / 453,499, filed March 21, 2023, and U.S. Provisional Application No. 63 / 454,771, filed March 27, 2023. The entire teachings of each of the above applications are incorporated herein by reference.

[0003] Government support

[0004] This invention was made with government support under Grant No. DE-SC0021832 awarded by the Department of Energy and Grant No. DE-AR0001242 awarded by ARPA-E. The government has certain rights in this invention. Background Art

[0005] Proton exchange membrane based fuel cell (PEMFC) is an eco-friendly energy conversion device that operates at low temperatures and is more efficient than existing internal combustion engines. With these advantages, PEMFC has become a popular alternative to fossil fuels in the transportation industry and has the potential to be used in a wide range of applications such as portable devices and stationary power systems.

[0006] The proton exchange membrane (PEM) that conducts protons and is used to separate the cathode from the anode is one of the most important elements of the PEMFC. The PEM significantly affects the overall performance of the fuel cell; therefore, improving the efficiency of the fuel cell requires a PEM with high ionic conductivity, low fuel permeation (crossover) and high physicochemical and mechanical stability. Because PEMFC uses a thin film as its electrolyte, these devices are more portable and compact than other types of fuel cells. However, the film also allows the permeation of fuel gas (hydrogen, H2), thereby adversely affecting the efficiency of the cell. Therefore, a PEM with high ionic conductivity and reduced hydrogen permeation is required. Summary of the invention

[0007] In a first embodiment, the present invention is a double-layer polyelectrolyte membrane comprising a first layer and a second layer, wherein: the first layer comprises perfluorosulfonic acid (PFSA), and the second layer comprises a cross-linked polysulfonated polymer, the cross-linked polysulfonated polymer comprising sulfonated polyphenylsulfone (sPPS), sulfonated polyetheretherketone (sPEEK), sulfonated polyphosphazene (sPOP), sulfonated polybenzimidazole (sPBI), sulfonated polyethersulfone (sPES), sulfonated polyphenylene oxide (sPPO), sulfonated polyaryletherketone (sPAEK), sulfonated polysulfone, sulfonated polysulfide sulfone, sulfonated polyimide (sPI), sulfonated polyetherimide (sPEI), sulfonated polyamine or a combination thereof, and wherein the first layer is disposed on the second layer.

[0008] In a second embodiment, the present invention is a method of making a double-layer polyelectrolyte membrane as described herein with respect to the first embodiment and various aspects thereof, the method comprising:

[0009] a) providing a first layer having a first side, and a solution or suspension comprising a polysulfonated polymer and a cross-linking agent,

[0010] b) coating a first side of the first layer with the solution or suspension, thereby producing a coated first layer;

[0011] c) exposing the coated first layer to conditions sufficient to cause a cross-linking reaction between the polysulfonated polymer and the cross-linking agent, thereby producing a bilayer polyelectrolyte membrane.

[0012] In a third embodiment, the present invention is a membrane electrode assembly (MEA) comprising: a double-layer polyelectrolyte membrane as described herein with respect to the first embodiment and its various aspects; a cathode; and an anode, wherein the double-layer electrolyte membrane is disposed between the anode and the cathode.

[0013] In a fourth embodiment, the invention is a fuel cell comprising one or more MEAs described herein with respect to the third embodiment and various aspects thereof and one or more gas flow bipolar plates. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] The foregoing will be apparent from the following more particular description of example embodiments of the invention.

[0015] Figure 1 Due to hydrogen permeation Schematic diagram of membrane degradation.

[0016] Figure 2 Schematic diagram showing that the presence of a cross-linked polymer layer on the PFSA layer results in reduced hydrogen permeation, thereby reducing degradation of the PFSA layer.

[0017] Figure 3 Graphs showing theoretically calculated values ​​of hydrogen permeation and electrical resistance of the coated PFSA membrane as a function of coating thickness are shown.

[0018] Figure 4 Shows 211 membrane and a membrane comprising a cross-linked sulfonated polyphenylsulfone (sPPS) coated thereon Cyclic voltammogram of the 211-layer film.

[0019] Figure 5 A graph is shown which demonstrates 211 film (square) and containing a sPPS layer coated Fuel cell polarization and power curves for a 211-layer membrane (diamonds).

[0020] Figure 6 A graph is shown which demonstrates 211 film and comprising a film coated with a cross-linked sPPS layer Results of Faster Accelerated Stress Testing (FAST) of 211-layer films.

[0021] Figure 7 A schematic diagram of a fuel cell containing a PEM is shown.

[0022] Figure 8 Shown is a graph demonstrating the water stability of sPPS before and after cross-linking.

[0023] Fig. 9 A graph showing the relationship between the degree of cross-linking and the conductivity of the cross-linked sPPS is shown.

[0024] Fig.10 A graph is shown which demonstrates the permeation of H2 through a 211 or comprising a cross-linked sPPS layer coated with different thicknesses 211 layers of membrane.

[0025] Fig.11 A graph is shown demonstrating the relationship between the thickness of the cross-linked sPPS coating and the durability of the resulting bilayer film.

[0026] Fig.12 A graph is shown which demonstrates the results of an accelerated stress test (AST) involving only 211 or comprising a cross-linked sPPS layer coated with different thicknesses H2 permeation of the 211-layer membrane as a function of time.

[0027] Fig.13A graph is shown, including fuel cell polarization curves, where the dashed line corresponds to the voltage-current curve (left axis) and the solid line corresponds to the current density curve (right axis). Squares indicate supported Base layer, triangle indication 211 base layer.

[0028] Fig.14 Graphs demonstrating the permeation of H2 through membranes comprising a base layer alone (dark line) or a base layer coated with a 1.5 μm coating of 40% cross-linked sPPS (light line) are shown.

[0029] Fig.15 The 25 μm 211 film, 1.5 μm 40% cross-linked sPPS film and 25 μm Area specific resistance values ​​of the bilayer films with 211 layers and 1.5 μm 40% cross-linked sPPS coating.

[0030] Fig.16 shows the sPPS 1 H NMR spectrum.

[0031] Fig.17 A graph is shown, containing 1.5 μm sPPS coated with various crosslinkers. The fuel cell polarization curve of 211, where the dashed line corresponds to the voltage-current curve (left axis) and the solid line corresponds to the current density curve (right axis). 1.3sHQ is coated with about 1.5μm sPPS 211, wherein each sPPS repeating unit is cross-linked with 1.3 2,5-dihydroxybenzenesulfonic acid molecules (30% cross-linking); 1.3HQ is coated with about 1.5 μm sPPS 211, wherein each sPPS repeating unit is cross-linked with 1.3 hydroquinone molecules (29% cross-linking); 1BP is coated with about 1.5 μm sPPS 211, where each sPPS repeating unit is cross-linked with 1 biphenyl molecule (32% cross-linking); 6EG is coated with about 1.5 μm sPPS 211, in which each sPPS repeating unit is cross-linked with 6 ethylene glycol molecules (40% cross-linking).

[0032] Fig.18 A graph showing the permeation of H2 through a 1.5 μm s PPS coating cross-linked with various cross-linking agents is shown. 211 film; 3sHQ: 0.513mA / cm 2 , 1.3HQ: 0.651mA / cm 2, 1BP: 0.737mA / cm 2 , 6EG: 0.736mA / cm 2 , 211:1.39mA / cm 2 .

[0033] Fig.19 A graph showing the polarization curves of a fuel cell comprising a bilayer membrane comprising a sPPS, sPPO or sPSU coated with a crosslinked hydroquinone 211, where the dotted line corresponds to the voltage-current curve (left axis), and the solid line corresponds to the current density curve (right axis). sPPS is coated with about 1.5 μm sPPS 211, wherein each sPPS repeating unit is cross-linked with 1.3 hydroquinone molecules (29% cross-linking); sPSU is coated with about 1.5 μm sPSU 211, wherein each sPSU repeating unit is cross-linked with 1.3 hydroquinone molecules (90% cross-linking); sPPO is coated with about 1.5 μm sPPO 211, in which each repeating unit is cross-linked with 0.5 hydroquinone molecules (90% cross-linking).

[0034] Fig. 20 A graph is shown showing the permeation of H2 through a substrate comprising sPPS, sPPO or sPSU coated with cross-linked hydroquinone. 211 double-layer membrane; sPPS: 0.651mA / cm 2 , sPSU: 1.216mA / cm 2 , sPPO: 1.903mA / cm 2 , Nafion 211: 1.39 mA / cm 2 (The curves are labeled with Fig.19 (same as in ).

[0035] The foregoing will become apparent from the following more particular description of example embodiments of the invention, as illustrated in the accompanying drawings, in which like reference numerals refer to the same parts throughout the different views. The drawings are not necessarily drawn to scale, emphasis instead being placed upon illustrating embodiments of the invention. DETAILED DESCRIPTION

[0036] Following is a description of example embodiments of the invention.

[0037] Hydrogen permeation is the undesired diffusion of hydrogen from the anode through the membrane to the cathode in a fuel cell. Hydrogen permeation can have at least three effects, including reduced fuel efficiency, reduced cathode potential, and formation of aggressive peroxide radicals. The permeated hydrogen can directly react with the oxygen at the cathode surface, resulting in a lower cathode potential than the cathode potential of the lower fuel cell. More seriously, this direct reaction between H2 and O2 at the cathode can produce peroxide radicals, which not only attack the catalyst layer, but also the membrane, resulting in significant catalyst layer and membrane degradation. In addition, it has been confirmed that hot spots or hydrogen peroxide formed by the highly exothermic chemical reaction between H2 and O2 can also cause pinholes in the membrane, thereby destroying the MEA and causing safety issues. This hydrogen permeation may also result in accelerated sintering of the catalyst.

[0038] In some embodiments, the present disclosure relates to a bilayer polyelectrolyte membrane that exhibits reduced hydrogen permeation. The membrane includes a perfluorosulfonic acid (PFSA) such as A layer of a cross-linked polysulfonated polyelectrolyte is provided, and a coating comprising a cross-linked polysulfonated polyelectrolyte. Sulfonated polyelectrolytes, such as polyphenylsulfone (sPPS), sulfonated polyetheretherketone (sPEEK), sulfonated polyphosphazene (sPOP), sulfonated polybenzimidazole (sPBI), sulfonated polyethersulfone (sPES), sulfonated polyphenylene oxide (sPPO), and sulfonated polyaryletherketone (sPAEK), sulfonated polysulfone, sulfonated polysulfide sulfone, sulfonated polyimide (sPI), sulfonated polyetherimide (sPEI) and sulfonated polyamine, can be used in the coating. Compared with PFSA, the coating has a lower hydrogen permeability, thereby reducing the permeation of hydrogen through the membrane ( Figure 1 and 2 ).

[0039] Figure 3 The graph in shows the design criteria for the coated membrane. The graph shows the theoretically calculated values ​​of H2 permeation and the resistance of the coated PFSA as a function of coating thickness. Figure 4 The cyclic voltammogram in 211 and coated with 1 μm cross-linked sPPS 211 Hydrogen permeation measurements. Figure 5 The graph in Figure 2 shows 211 and coated with 1 μm cross-linked sPPS coating 211 fuel cell polarization and power curves. These data show that compared with the uncoated The polymer coating reduced H2 permeation by 44% compared to 211. Figure 6 Results from the Faster Accelerated Stress Test (FAST) in the study showed that the presence of the cross-linked sPPS coating nearly doubled the durability of the membrane. The membrane failure time of 211 was about 5000 equivalent hours, while that of 1 μm cross-linked sPPS coating was The time to failure of 211 is about 9500 equivalent hours.

[0040] definition

[0041] Numerical ranges include numbers that define the range. For example, "x is an integer between 5 and 14" means that x can be 5, 6, 7, 8, 9, 10, 11, 12, 13 or 14. Taking into account significant figures and errors associated with measurement, measured values ​​and measurable values ​​should be understood as approximate values. As used in this application, the terms "about" and "approximately" have the meanings understood in the art; using one of them instead of the other does not necessarily mean a different range. Unless otherwise specified, the numbers used in this application, whether or not with modified terms such as "about" or "approximately", should be understood to cover normal deviations and / or fluctuations as understood by ordinary technicians in the relevant field. In certain embodiments, the term "about" or "approximately" refers to a series of values ​​falling in either direction of the stated reference value (greater than or less than the stated reference value) of 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1% or less, unless otherwise specified or otherwise obvious from the context (except when such a number exceeds 100% of the possible value).

[0042] As used herein, the term "double-layer polyelectrolyte membrane" refers to a membrane containing two layers disposed on top of each other, each layer comprising a polyelectrolyte. The two layers may be adhered to each other by the formation of chemical bonds or by van der Waals interactions.

[0043] As used herein, the term "polysulfonated polymer" or "sulfonated polymer" refers to a polymer containing multiple sulfonic acid or sulfonate groups: S(O)2OH or S(O)2O - M + , where M + For the counter ion.

[0044] As used herein, the term "degree of sulfonation" refers to the number of repeating units having at least one sulfonic acid / sulfonate group. For example, a 20% degree of sulfonation means that 20% of the repeating units of the polymer are sulfonated, while a 100% degree of sulfonation means that each repeating unit in the polymer contains one sulfonic acid / sulfonate group. This may include polymers containing multiple sulfonic acid / sulfonate groups (e.g., disulfonated, trisulfonated, tetrasulfonated, etc.) per repeating unit. In some embodiments, the sulfonated polymer may contain an average of 2 sulfonic acid groups per repeating unit, which corresponds to a 200% degree of sulfonation. In some embodiments, the sulfonated polymer may contain an average of 2, 3, 4, or 5 sulfonic acid groups per repeating unit, which corresponds to 200%, 300%, 400%, or 500% degrees of sulfonation, respectively. In some embodiments, the sulfonated polymer may contain an average of 1.5 to 2.5 sulfonic acid groups per repeating unit, which corresponds to a 150% to 200% degree of sulfonation.

[0045] The sulfonated polymers of the present disclosure can also be characterized by the average number of sulfonic acid groups per repeating unit. For example, sulfonated polyphenylsulfone (sPPS) can contain 1, 2, 3, 4, 5, 6, 7, or 8 sulfonic acid groups per repeating unit. For example, a repeating unit of sPPS can contain 2 sulfonic acid groups: Alternatively, the repeating unit of sPPS may contain 4 or 6 sulfonic acid groups:

[0046] In a given polymer, some repeating units may have, for example, 1 sulfonic acid group, some repeating units may have 2 sulfonic acid groups, and some repeating units may have 3 or more sulfonic acid groups. 1 The number of sulfonic acid groups per repeating unit measured in the bulk polymer by H NMR spectroscopy or ion exchange capacity corresponds to the average number of sulfonic acid groups over all repeating units of the polymer.

[0047] As used herein, the term "polyphenylsulfone" refers to a polymer comprising the following repeating units:

[0048]

[0049] The sulfonated polyphenylene sulfone may contain 1, 2, 3, 4, 5, 6, 7 or 8 sulfonic acid groups per repeating unit.

[0050] As used herein, the term "polyetheretherketone" refers to a polymer comprising the following repeating units:

[0051]

[0052] The sulfonated polyetheretherketone may contain 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12 sulfonic acid groups per repeat unit.

[0053] As used herein, the term "polyphosphazene" refers to a polymer comprising the following repeating units:

[0054]

[0055] As used herein, the term "polybenzimidazole" refers to a polymer comprising the following repeating units:

[0056]

[0057] The sulfonated polybenzimidazole may contain 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 sulfonic acid groups per repeat unit.

[0058] As used herein, the term "polyethersulfone" refers to a polymer comprising the following repeating units:

[0059]

[0060] The sulfonated polyethersulfone may contain 1, 2, 3, 4, 5, 6, 7 or 8 sulfonic acid groups per repeating unit.

[0061] As used herein, the term "polyphenylene ether" refers to a polymer comprising the following repeating units:

[0062]

[0063] The sulfonated polyphenylene ether may contain 1 or 2 sulfonic acid groups per repeating unit.

[0064] As used herein, the term "polyaryletherketone" refers to a polymer comprising one or more of the following repeating units:

[0065]

[0066] The sulfonated polyaryletherketones may contain 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20 sulfonic acid groups per repeat unit.

[0067] As used herein, the term "polysulfone" refers to a polymer comprising the following repeating units:

[0068]

[0069] The sulfonated polysulfone (sPSU) may contain 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or 16 sulfonic acid groups per repeating unit.

[0070] As used herein, the term "polysulfide sulfone" refers to a polymer comprising the following repeating units:

[0071]

[0072] The sulfonated polythioethersulfone may contain 1, 2, 3, 4, 5, 6, 7 or 8 sulfonic acid groups per repeating unit.

[0073] As used herein, the term "polyimide" refers to a polymer comprising the following repeating units:

[0074]

[0075] The sulfonated polyimide may contain 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 sulfonic acid groups per repeat unit.

[0076] As used herein, the term "polyetherimide" refers to a polymer comprising the following repeating units:

[0077]

[0078] The sulfonated polyetherimide can contain 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17 or 18 sulfonic acid groups per repeat unit.

[0079] Any of the above polymer repeating units may have one or more hydrogen atoms replaced by -CN, -NO2, -N3, -OH, F, Cl, Br, I, oxo, -SO2H, -SO3H, -OR aa 、-NH(R aa )2、-N(R aa )2、-N(R aa )3 + X - , -SH, -SR aa 、-C(=O)R aa 、-CO2H、-CHO、-CO2R aa 、-OC(=O)R aa 、-OCO2R aa 、-C(=O)N(R aa )2, -OC(=O)N(R aa )2.-NR aa C(=O)R aa 、-NR aa CO2R aa 、-NR aa C(=O)N(R aa )2, -C(=NR aa )R aa、-C(=O)NR aa S02R aa 、-NR aa S02R aa 、-SO2N(R aa 2. -SO2R aa 、-SO2OR aa 、-OSO2R aa 、-S(=O)R aa 、-OS(=O)R aa 、-Si(R aa )3.-OSi(R aa 3. C 1-12 Alkyl, C 1-12 Alkoxy, C 1-12 Haloalkyl, C 3-12 Cycloalkyl, 3-16 membered heterocyclic group and C 6-12 substituted with aryl, wherein X – is the counter ion and R aa Each instance of is independently selected from H, -OH, C 1-10 Alkyl, C 1-10 Haloalkyl, C 3-12 Cycloalkyl, 5-16 membered heterocyclic group and C 6-12 Aryl, or two R aa The groups are linked to form a 3-16 membered heterocyclic group.

[0080] As used herein, the term "polyol" refers to an alcohol containing more than one hydroxyl group. Examples of polyols include, but are not limited to, ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, glycerol, erythriol, xylitol, hydroquinone, catechol, resorcinol, and phloroglucinol.

[0081] As used herein, the term "polyelectrolyte" refers to a polymer comprising repeating units with charged or ionizable groups. Under a particular set of conditions, a polyelectrolyte has a net negative charge or a net positive charge. In some embodiments, a polyelectrolyte is or comprises a polycation; in some embodiments, a polyelectrolyte is or comprises a polyanion. A polycation has a net positive charge and a polyanion has a net negative charge. The net charge of a given polyelectrolyte may depend on the surrounding chemical conditions, for example, on pH.

[0082] As used herein, the term "perfluorosulfonic acid" refers to a polymer having the following structural formula:

[0083]

[0084] Where R frepresents a perfluoroalkylene or perfluorooxyalkylene group, and x and y represent the relative proportions of perfluoromonomer and sulfonated monomer, respectively. As used herein, the term "perfluoroalkylene" or "perfluorooxyalkylene" refers to an alkylene or oxyalkylene group in which all hydrogen atoms have been replaced by fluorine. One type of PFSA is represented by structural formula (I):

[0085]

[0086] Such PFSAs are usually classified according to the length of their side chains. For example, (Formerly Dow SSC) PFSAs are generally classified as short side chain (SSC) PFSAs, while Considered to be long side chain (LSC) PFSA. Examples of commercially available PFSA include the following:

[0087]

[0088] As used herein, the term "crosslinking" refers to the formation of covalent or ionic bonds between the sulfonic acid groups of the sulfonated polymer and the crosslinking agent. For example, crosslinking refers to the formation of sulfonates due to the reaction between the sulfonic acid groups of the sulfonated polymer and a polyol. In some embodiments, crosslinking refers to the formation of sulfonamides due to the reaction between the sulfonic acid groups of the sulfonated polymer and a polyamine. As used herein, the term "crosslinking" does not refer to the formation of covalent or ionic bonds between the crosslinking agent and any functional group in the polymer repeating unit other than the sulfonic acid group.

[0089] As used herein, the term "crosslinked polymer" refers to a polymer in which two or more non-adjacent repeating units of the same backbone are linked via a crosslinking moiety. The term "crosslinked polymer" also refers to two or more different backbones linked via multiple crosslinking moieties.

[0090] As used herein, the term "crosslinking moiety" refers to a multivalent moiety, such as a divalent or trivalent moiety, that forms a covalent bond with one or more non-adjacent repeating units of the same polymer backbone or with one or more repeating units of different backbones. The crosslinking moiety may comprise a charged group, such as an ammonium group or a metal ion, that forms an electrostatic / ionic bond with the sulfonic acid group attached to the repeating unit of the sulfonated polymer.

[0091] As used herein, the term "cross-linking reaction" refers to a chemical reaction between the sulfonic acid groups attached to the repeating units of the sulfonated polymer and the cross-linking agent, which results in the formation of covalent or electrostatic / ionic bonds between the polymer chains and the cross-linking agent.

[0092] As used herein, the term "conditions sufficient to allow the polymer and the crosslinking agent to undergo a crosslinking reaction" refers to the external stimulus (e.g., heat, UV light, microwave irradiation, the presence of a chemical initiator such as a free radical initiator) and time required to form a crosslinked polymer.

[0093] As used herein, the term "gel fraction (%)" is calculated based on the following formula: [[M(f) / [M(i)]]*100, where M(f) is the dry mass of the film exposed to a solvent that dissolves the original polymer and crosslinker, and M(i) is the dry mass of the film before exposure to the dissolving solvent. The gel fraction represents the percentage of polymer and linker remaining in the network after exposure to a solvent that dissolves each individual component.

[0094] As used herein, the term "repeat unit" (also called monomer unit) refers to a chemical moiety that repeats itself periodically to produce a complete polymer chain (excluding terminal groups) by successively linking the repeat units together. A polymer may contain one or more different repeat units.

[0095] As used herein, the "backbone" of a polymer or the "backbone" of a polymer is a series of bonded atoms that together produce a continuous chain of molecules. As used herein, the "side chains" of a polymer are a series of bonded atoms that are pendant from the main chain of a polymer.

[0096] As used herein, "PFSA and matrix polymer form an interpenetrating network" refers to a porous matrix containing PFSA in its pores. The porous matrix can be impregnated with PFSA, for example, by soaking the matrix in a solution of PFSA or by spraying a solution of PFSA on the porous matrix. Alternatively, the porous matrix can be impregnated with a solution of PFSA monomers, followed by polymerization within the pores of the matrix.

[0097] As used herein, "unsupported membrane" refers to a membrane containing only a PFSA layer and a cross-linked polysulfonated polymer layer without any other layers, supports or reinforcements.

[0098] As used herein, the term "continuous layer" refers to a layer that contains no gaps or openings, such that any point on the layer can be connected to any other point on the layer by a straight line, and each point of the straight line belongs to the layer.

[0099] As used herein, the term "alkyl" refers to a straight-chain or branched saturated hydrocarbon group having 1 to 10 carbon atoms ("C 1–10 In some embodiments, an alkyl group has 1 to 9 carbon atoms (“C 1–9 In some embodiments, an alkyl group has 1 to 8 carbon atoms (“C 1–8 In some embodiments, an alkyl group has 1 to 7 carbon atoms (“C 1–7 In some embodiments, an alkyl group has 1 to 6 carbon atoms (“C 1–6 In some embodiments, an alkyl group has 1 to 5 carbon atoms (“C1–5 In some embodiments, an alkyl group has 1 to 4 carbon atoms (“C 1–4 In some embodiments, an alkyl group has 1 to 3 carbon atoms (“C 1–3 In some embodiments, an alkyl group has 1 to 2 carbon atoms (“C 1–2 In some embodiments, an alkyl group has 1 carbon atom ("C1 alkyl"). In some embodiments, an alkyl group has 2 to 6 carbon atoms ("C 2–6 C 1-6 Examples of alkyl groups include methyl (C1), ethyl (C2), propyl (C3) (e.g., n-propyl, isopropyl), butyl (C4) (e.g., n-butyl, tert-butyl, sec-butyl, isobutyl), pentyl (C5) (e.g., n-pentyl, 3-pentyl, amyl, neopentyl, 3-methyl-2-butyl, tert-pentyl) and hexyl (C6) (e.g., n-hexyl). Additional examples of alkyl groups include n-heptyl (C7), n-octyl (C8), etc. Unless otherwise specified, each instance of an alkyl group is independently unsubstituted ("unsubstituted alkyl") or substituted ("substituted alkyl") with one or more substituents (e.g., halogen, such as F). In certain embodiments, an alkyl group is an unsubstituted C 1-10 Alkyl (such as unsubstituted C 1-6 Alkyl, for example, -CH3(Me), unsubstituted ethyl (Et), unsubstituted propyl (Pr, for example, unsubstituted n-propyl (n-Pr), unsubstituted isopropyl (i-Pr)), unsubstituted butyl (Bu, for example, unsubstituted n-butyl (n-Bu), unsubstituted tert-butyl (tert-Bu or t-Bu), unsubstituted sec-butyl (sec-Bu), unsubstituted isobutyl (i-Bu)). In certain embodiments, the alkyl group is substituted C 1-10 Alkyl (such as substituted C 1-6 Alkyl, e.g., -CF3, Bn).

[0100] As used herein, the term "alkenyl" refers to a straight or branched chain hydrocarbon group ("C 2-10 In some embodiments, an alkenyl group has 2 to 9 carbon atoms ("C 2-9 In some embodiments, an alkenyl group has 2 to 8 carbon atoms (“C 2-8 In some embodiments, an alkenyl group has 2 to 7 carbon atoms (“C 2-7In some embodiments, an alkenyl group has 2 to 6 carbon atoms (“C 2-6 In some embodiments, an alkenyl group has 2 to 5 carbon atoms (“C 2-5 In some embodiments, an alkenyl group has 2 to 4 carbon atoms (“C 2-4 In some embodiments, an alkenyl group has 2 to 3 carbon atoms (“C 2-3 In some embodiments, an alkenyl group has 2 carbon atoms ("C2 alkenyl"). The one or more carbon-carbon double bonds may be internal (such as in 2-butenyl) or terminal (such as in 1-butenyl). 2–4 Examples of alkenyl groups include, but are not limited to, ethenyl (C2), 1-propenyl (C3), 2-propenyl (C3), 1-butenyl (C4), 2-butenyl (C4), etc. 2–6 Examples of the alkenyl group include the aforementioned C 2–4 In some embodiments, the alkenyl group is an unsubstituted C 1-1, ... 2-10 In certain embodiments, the alkenyl group is a substituted C 2-10 Alkenyl.

[0101] As used herein, the term "alkynyl" refers to a straight or branched chain hydrocarbon group ("C 2-10 In some embodiments, an alkynyl group has 2 to 9 carbon atoms ("C 2–9 In some embodiments, an alkynyl group has 2 to 8 carbon atoms (“C 2–8 In some embodiments, an alkynyl group has 2 to 7 carbon atoms (“C 2–7 In some embodiments, an alkynyl group has 2 to 6 carbon atoms (“C 2–6 In some embodiments, an alkynyl group has 2 to 5 carbon atoms (“C 2–5 In some embodiments, an alkynyl group has 2 to 4 carbon atoms (“C 2–4 In some embodiments, an alkynyl group has 2 to 3 carbon atoms (“C 2–3In some embodiments, an alkynyl group has 2 carbon atoms ("C2 alkynyl"). The one or more carbon-carbon triple bonds can be internal (such as in 2-butynyl) or terminal (such as in 1-butynyl). C 2–4 Examples of alkynyl groups include, but are not limited to, ethynyl (C2), 1-propynyl (C3), 2-propynyl (C3), 1-butynyl (C4), 2-butynyl (C4), and the like. 2–6 Examples of the alkynyl group include the aforementioned C 2–4 In some embodiments, the alkynyl group is an unsubstituted C alkynyl group, and pentynyl (C5), hexynyl (C6), and the like. Additional examples of alkynyl groups include heptynyl (C7), octynyl (C8), and the like. Unless otherwise specified, each instance of an alkynyl group is independently unsubstituted (an “unsubstituted alkynyl”) or substituted (a “substituted alkynyl”) with one or more substituents. In certain embodiments, an alkynyl group is an unsubstituted C 2-10 In certain embodiments, the alkynyl group is a substituted C 2-10 Alkynyl.

[0102] The term "aryl" refers to a group having 6-14 ring carbon atoms and zero heteroatoms provided in the aromatic ring system, a monocyclic or polycyclic (e.g., bicyclic or tricyclic) 4n+2 aromatic ring system (e.g., having 6, 10, or 14 π electrons in common in the ring array) ("C 6-14 In some embodiments, an aryl group has 6 ring carbon atoms ("C6 aryl"; e.g., phenyl). In some embodiments, an aryl group has 10 ring carbon atoms ("C 10 In some embodiments, an aryl group has 14 ring carbon atoms ("C 14 "Aryl" also includes ring systems in which an aryl ring as defined above is fused to one or more carbocyclyl or heterocyclyl groups, wherein the radical or point of attachment is on the aryl ring, and in such cases the number of carbon atoms continues to refer to the number of carbon atoms in the aryl ring system. Unless otherwise specified, each instance of an aryl group is independently unsubstituted (an "unsubstituted aryl") or substituted (a "substituted aryl") with one or more substituents. In certain embodiments, an aryl group is an unsubstituted C 6-14 In certain embodiments, the aryl group is a substituted C 6-14 Aryl.

[0103] The term "haloalkyl" refers to a substituted alkyl group in which one or more hydrogen atoms are independently replaced by a halogen, e.g., fluorine, bromine, chlorine, or iodine. In some embodiments, the haloalkyl moiety has 1 to 12 carbon atoms ("C 1-12In some embodiments, the haloalkyl moiety has 1 to 6 carbon atoms (“C 1-6 In some embodiments, the haloalkyl moiety has 1 to 4 carbon atoms (“C 1-4 In some embodiments, the haloalkyl moiety has 1 to 3 carbon atoms (“C 1-3 In some embodiments, the haloalkyl moiety has 1 to 2 carbon atoms (“C 1-2 "haloalkyl"). Examples of haloalkyl groups include -CHF2, -CH2F, -CF3, -CH2CF3, -CF2CF3, -CF2CF2CF3, -CCl3, -CFCl2, -CF2Cl, and the like.

[0104] The term "sulfonic acid group" refers to the following group: -S(O)2OH.

[0105] The term "sulfonate" refers to a salt or ester of a sulfonic acid, -S(O)2OR, wherein R represents a cation, such as a metal or ammonium cation, or an aliphatic or aromatic substituent. Examples of sulfonates include salts such as lithium sulfonate, sodium sulfonate, potassium sulfonate, or ammonium sulfonate. In some embodiments, the term "sulfonate" refers to an ester of a sulfonic acid, for example, an optionally substituted C 1-12 Alkyl sulfonate or optionally substituted C 6-12 In some embodiments, R is a multivalent (e.g., divalent or trivalent) group that forms a covalent or ionic bond with one or more sulfonic acid groups attached to the same or different sulfonated polymer chains, thereby forming a crosslinking moiety together with the two or more -S(O)2O- groups to which it is attached.

[0106] The term "sulfonamide" refers to the amide of a sulfonic acid, -S(O)2NRR', wherein R and R' are each hydrogen or an optionally substituted aliphatic or aromatic substituent, such as an optionally substituted C 1-12 Alkyl or optionally substituted C 6-12 In some embodiments, R and / or R' are each a multivalent (e.g., divalent or trivalent) group that forms a covalent or ionic bond with one or more sulfonic acid groups attached to the same or different sulfonated polymer chains, thereby forming a crosslinking moiety together with the two or more -S(O)2O- groups to which it is attached.

[0107] Adding the suffix "-ene" to a group indicates that the group is a divalent moiety, for example, alkylene is a divalent moiety of an alkyl group, alkenylene is a divalent moiety of an alkenyl group, alkynylene is a divalent moiety of an alkynyl group, and arylene is a divalent moiety of an aryl group.

[0108] The term "substituted" refers to a moiety with a substituent that replaces hydrogen on one or more carbons of the skeleton. It should be understood that "replacement" or "substituted by..." includes implicit conditions, i.e., such substitution is consistent with the allowed valence of the substituted atom and the substituent, and the substitution produces a stable compound, for example, a compound that does not spontaneously undergo transformation, such as by rearrangement, cyclization, elimination, etc. As used herein, the term "substituted" is intended to include all allowed substituents of organic compounds. In a broad sense, allowed substituents include acyclic and cyclic, branched and unbranched, carbocyclic and heterocyclic, aromatic and non-aromatic substituents of organic compounds. For appropriate organic compounds, allowed substituents may be one or more and the same or different. For purposes of the present invention, heteroatoms such as nitrogen may have hydrogen substituents and / or any allowed substituents of organic compounds described herein that satisfy the valence of heteroatoms. Substituents may include any substituent described herein, for example, halogen, hydroxyl, carbonyl (such as carboxyl, alkoxycarbonyl, formyl or acyl), thiocarbonyl (such as thioester, thioacetate or thioformate), alkoxy, phosphoryl, phosphate, phosphonate, phosphinate, amino, amido, amidino, imino, cyano, nitro, azido, sulfhydryl, alkylthio, sulfate, sulfonate, sulfamoyl, sulfonamido, sulfonyl, heterocyclyl, aralkyl or aromatic or heteroaromatic moiety. It will be appreciated by those skilled in the art that the substituents themselves may be substituted if appropriate. Unless explicitly stated as "unsubstituted", references to chemical moieties herein are understood to include substituted variants. For example, references to "aryl" groups or moieties implicitly include both substituted and unsubstituted variants.

[0109] Exemplary carbon atom substituents include, but are not limited to, halogen, -CN, -NO2, -N3, -OH, F, Cl, Br, I, oxo, -SO2H, -SO3H, -OR aa 、-NH(R aa )2、-N(R aa )2、-N(R aa )3 + X - , -SH, -SR aa 、-C(=O)R aa 、-CO2H、-CHO、-CO2R aa 、-OC(=O)R aa 、-OCO2R aa 、-C(=O)N(R aa )2, -OC(=O)N(R aa )2.-NR aa C(=O)R aa 、-NR aa CO2R aa 、-NRaa C(=O)N(R aa )2, -C(=NR aa )R aa 、-C(=O)NR aa S02R aa 、-NR aa S02R aa 、-SO2N(R aa 2. -SO2R aa 、-SO2OR aa 、-OSO2R aa 、-S(=O)R aa 、-OS(=O)R aa 、-Si(R aa )3.-OSi(R aa 3. C 1-12 Alkyl, C 1-12 Haloalkyl, 3-16 membered heterocyclic group and C 6-12 Aryl, wherein X – is the counter ion and R aa Each instance of is independently selected from H, -OH, C 1-10 Alkyl, C 1-10 Haloalkyl, C 3-12 Cycloalkyl, 5-16 membered heterocyclic group and C 6-12 Aryl, or two R aa The groups are linked to form a 3-16 membered heterocyclic group.

[0110] In a first embodiment, the present invention is a double-layer polyelectrolyte membrane comprising a first layer and a second layer, wherein: the first layer comprises perfluorosulfonic acid (PFSA), and the second layer comprises a cross-linked polysulfonated polymer, the cross-linked polysulfonated polymer comprising sulfonated polyphenylsulfone (sPPS), sulfonated polyetheretherketone (sPEEK), sulfonated polyphosphazene (sPOP), sulfonated polybenzimidazole (sPBI), sulfonated polyethersulfone (sPES), sulfonated polyphenylene oxide (sPPO), sulfonated polyaryletherketone (sPAEK), sulfonated polysulfone (sPSU), sulfonated polysulfide sulfone, sulfonated polyimide (sPI), sulfonated polyetherimide (sPEI), sulfonated polyamine or a combination thereof, and wherein the first layer is disposed on the second layer.

[0111] In a first aspect of the first embodiment, the PFSA is a polymer comprising a repeating unit represented by structural formula (I):

[0112]

[0113] wherein x is an integer between 1 and 15, m is an integer between 0 and 2, n is an integer between 1 and 5, and represents the connection point with the adjacent repeating unit. For example, x is an integer between 5 and 14, m is 1 or 2, and n is 2 or 3. In some cases, m is 1 and n is 2.

[0114] In a second aspect of the first embodiment, the PFSA is a polymer comprising about 500 to about 1500 repeating units represented by structural formula (I): for example, the PFSA is a polymer comprising about 600 to about 1400, about 700 to about 1300, about 800 to about 1200, or about 900 to about 1100 repeating units represented by structural formula (I). For example, the PFSA is a polymer comprising about 1000 repeating units represented by structural formula (I). The remaining features and exemplary features of the second aspect are as described above with respect to the first aspect of the first embodiment.

[0115] In a third aspect of the first embodiment, the cross-linked polysulfonated polymer comprises sulfonated polyphenylsulfone (sPPS), sulfonated polyetheretherketone (sPEEK), sulfonated polyphosphazene (sPOP), sulfonated polybenzimidazole (sPBI), sulfonated polyethersulfone (sPES), sulfonated polyaryletherketone (sPAEK), sulfonated polysulfone (sPSU), sulfonated polysulfide sulfone, sulfonated polyimide (sPI), sulfonated polyetherimide (sPEI), sulfonated polyamine, or a combination thereof. For example, the cross-linked polysulfonated polymer comprises sPPS, sPES, sPSU, sulfonated polysulfide sulfone, or a combination thereof. For example, the cross-linked polysulfonated polymer comprises sPPS, sPES, sPSU, sulfonated polysulfide sulfone, or a combination thereof. For example, the cross-linked polysulfonated polymer comprises sPPS, sPES, sPSU, or a combination thereof. For example, the cross-linked polysulfonated polymer comprises sPPS, sPEEK, sPOP, or sPBI. For example, the cross-linked polysulfonated polymer comprises sPPS or sPSU. For example, the cross-linked polysulfonated polymer comprises sPPS. The remaining features and exemplary features of the third aspect are as described above in relation to the first and second aspects of the first embodiment.

[0116] In a fourth aspect of the first embodiment, the cross-linked polysulfonated polymer comprises a cross-linking moiety represented by one of the following structural formulas:

[0117]

[0118]

[0119] Where R 1 , R 2 , R 3 and R 4 Each of which is independently selected from H, C 1-12 Alkyl, C 1-12 Haloalkyl, C 6-12 Aryl and C 6-14 Aryl (C 1-12 M 2+ Selected from Mr.2+ , Ca 2+ , Ba 2+ and Al(X) 2+ , wherein X is a halogen, acetate or nitrate; and Represents the point of attachment of the crosslinking moiety to the repeating unit of the crosslinked polysulfonated polymer. For example, the crosslinking moiety is represented by one of the following structural formulas: For example, the cross-linking moiety is represented by one of the following structural formulas: The remaining features and exemplary features of the fourth aspect are as described above with respect to the first to third aspects of the first embodiment.

[0120] In a fifth aspect of the first embodiment, the first layer further comprises a porous matrix comprising a matrix polymer, wherein the PFSA and the matrix polymer form an interpenetrating network. For example, the first layer comprises about 50 wt % to about 99 wt % PFSA, about 55 wt % to about 98 wt % PFSA, about 60 wt % to about 97 wt % PFSA, about 70 wt % to about 96 wt % PFSA, or about 80 wt % to about 96 wt % PFSA. For example, the first layer comprises about 70 wt % to about 99 wt % PFSA, such as about 78 wt % to about 95 wt % PFSA. The remaining features and exemplary features of the fifth aspect are as described above with respect to the first to fourth aspects of the first embodiment.

[0121] In a sixth aspect of the first embodiment, the matrix polymer is polytetrafluoroethylene (PTFE). For example, the matrix polymer is expanded PTFE (ePTFE). The remaining features and exemplary features of the sixth aspect are as described above with respect to the first to fifth aspects of the first embodiment.

[0122] In a seventh aspect of the first embodiment, the cross-linked polysulfonated polymer has a degree of sulfonation of from about 10% to about 400%. For example, the cross-linked polysulfonated polymer has a degree of sulfonation of from about 10% to about 100%, from about 20% to about 100%, from about 30% to about 100%, from about 40% to about 100%, from about 50% to about 100%, from about 60% to about 100%, from about 70% to about 100%, from about 80% to about 100%, from about 50% to about 200%, from about 80% to about 200%, from about 100% to about 200%, from about 100% to about 250%, or from about 100% to about 250%. 0%, about 150% to about 200%, about 100% to about 300%, about 100% to about 350%, about 100% to about 400%, about 150% to about 250%, about 150% to about 300%, about 150% to about 350%, about 150% to about 400%, about 200% to about 300%, about 200% to about 350%, about 200% to about 400%, or about 250% to about 350%. For example, the degree of sulfonation of the cross-linked polysulfonated polymer is about 20%, about 30%, about 40%, about 50%, about 60%, about 70%, about 80%, about 90%, about 100%, about 120%, about 140%, about 160%, about 180%, about 200%, about 220%, about 240%, about 260%, about 280%, about 300%, about 320%, about 340%, about 360%, about 380%, or about 400%. For example, the degree of sulfonation of the cross-linked polysulfonated polymer is about 30% to about 90%, about 40% to about 80%, or about 50% to about 60%. The remaining features and exemplary features of the seventh aspect are as described above with respect to the first to sixth aspects of the first embodiment.

[0123] In an eighth aspect of the first embodiment, the crosslinked polysulfonated polymer has a gel fraction of about 50% to about 100%. For example, the crosslinked polysulfonated polymer has a gel fraction of about 50%, about 60%, about 70%, about 80%, about 90%, or about 100%. The remaining features and exemplary features of the eighth aspect are as described above with respect to the first to seventh aspects of the first embodiment.

[0124] In the ninth aspect of the first embodiment, the thickness of the first layer is about 5 μm to about 200 μm. For example, the thickness of the first layer is about 5 μm, about 10 μm, about 15 μm, about 20 μm, about 25 μm, about 30 μm, about 35 μm, about 40 μm, about 45 μm, about 50 μm, about 55 μm, about 60 μm, about 65 μm, about 70 μm, about 75 μm, about 80 μm, about 85 μm, about 90 μm, about 95 μm, about 100 μm, about 110 μm, about 120 μm, about 130 μm, about 140 μm, about 150 μm, about 160 μm, or about 170 μm, about 180 μm, about 190 μm or about 200 μm. For example, the thickness of the first layer is about 5 μm to about 175 μm. For example, the thickness of the first layer is about 25 μm. The remaining features and exemplary features of the ninth aspect are as described above with respect to the first to eighth aspects of the first embodiment.

[0125] In a tenth aspect of the first embodiment, the second layer has a thickness of about 0.2 μm to about 175 μm. For example, the thickness of the second layer is about 0.2 μm, about 0.4 μm, about 0.6 μm, about 0.8 μm, about 1.0 μm, about 2.0 μm, about 3.0 μm, about 4.0 μm, about 5 μm, about 10 μm, about 15 μm, about 20 μm, about 25 μm, about 30 μm, about 35 μm, about 40 μm, about 45 μm, about 50 μm, about 55 μm, about 60 μm, about 65 μm, about 70 μm, about 75 μm, about 80 μm, about 85 μm, about 90 μm, about 95 μm, about 100 μm, about 110 μm, about 120 μm, about 130 μm, about 140 μm, about 150 μm, about 160 μm or about 170 μm. For example, the thickness of the second layer is about 0.2 μm to about 10 μm, about 0.4 μm to about 5 μm, about 0.6 μm to about 2 μm, about 0.8 μm to about 1.5 μm. For example, the thickness of the second layer is about 0.75 μm. For example, the thickness of the second layer is about 1 μm. For example, the thickness of the second layer is about 1.5 μm. The remaining features and exemplary features of the tenth aspect are as described above with respect to the first to ninth aspects of the first embodiment.

[0126] In an eleventh aspect of the first embodiment, the first layer is continuous. The remaining features and exemplary features of the eleventh aspect are as described above with respect to the first to tenth aspects of the first embodiment.

[0127] In a twelfth aspect of the first embodiment, the membrane is unsupported. The remaining features and exemplary features of the twelfth aspect are as described above with respect to the first to eleventh aspects of the first embodiment.

[0128] In a thirteenth aspect of the first embodiment, the PFSA is a polymer comprising a repeating unit represented by structural formula (I):

[0129]

[0130] wherein x is an integer between 5 and 14, m is 1 or 2, and n is 2 or 3; and the cross-linked polysulfonated polymer comprises sPPS and a cross-linking moiety represented by one of the following structural formulas: The remaining features and exemplary features of the thirteenth aspect are as described above with respect to the first to twelfth aspects of the first embodiment.

[0131] In a fourteenth aspect of the first embodiment, the first layer comprises a porous substrate, the porous substrate comprising a matrix polymer, and wherein the PFSA and the matrix polymer form an interpenetrating network; the PFSA is a polymer comprising a repeating unit represented by structural formula (I):

[0132]

[0133] wherein x is an integer between 5 and 14, m is 1 or 2, and n is 2 or 3; the matrix polymer comprises ePTFE; and the crosslinked polysulfonated polymer comprises sPPS and a crosslinking moiety represented by one of the following structural formulas: The remaining features and exemplary features of the fourteenth aspect are as described above with respect to the first to thirteenth aspects of the first embodiment.

[0134] In the fifteenth aspect of the first embodiment, the cross-linked polysulfonated polymer is a sulfonated polyphenylsulfone (sPPS), a sulfonated polyetheretherketone (sPEEK), a sulfonated polyphosphazene (sPOP), a sulfonated polybenzimidazole (sPBI), a sulfonated polyethersulfone (sPES), a sulfonated polyaryletherketone (sPAEK), a sulfonated polysulfone (sPSU), a sulfonated polysulfide sulfone, a sulfonated polyimide (sPI), a sulfonated polyetherimide (sPEI), a sulfonated polyamine, or a combination thereof. For example, the cross-linked polysulfonated polymer is sPPS, sPES, sPSU, a sulfonated polysulfide sulfone, or a combination thereof. For example, the cross-linked polysulfonated polymer is sPPS, sPES, sPSU, a sulfonated polysulfide sulfone, or a combination thereof. For example, the cross-linked polysulfonated polymer is sPPS, sPEEK, sPOP, or sPBI. For example, the cross-linked polysulfonated polymer is sPPS or sPSU. For example, the cross-linked polysulfonated polymer is sPPS. The remaining features and exemplary features of the third aspect are as described above in relation to the first and second aspects of the first embodiment.

[0135] The remaining features and exemplary features of the fifteenth aspect are as described above with respect to the first to fourteenth aspects of the first embodiment.

[0136] In a sixteenth aspect of the first embodiment, the cross-linked polysulfonated polymer comprises a cross-linking moiety represented by one of the following structural formulas:

[0137]

[0138]

[0139] Where R 1 , R 2 , R 3 and R 4 Each of which is independently selected from H, C 1-12 Alkyl, C 1-12 Haloalkyl, C 6-14 Aryl and C 6-14 Aryl (C 1-12 Alkylene); R 5 is H or -SO3H, M 2+ Selected from Mr. 2+ , Ca 2+ , Ba 2+ and Al(X) 2+ , wherein X is halogen, acetate or nitrate; k is 1, 2, 3 or 4, and Represents the point of attachment of the crosslinking moiety to the repeating unit of the crosslinked polysulfonated polymer. For example, the crosslinking moiety is represented by one of the following structural formulas:

[0140] For example, the cross-linking moiety is represented by one of the following structural formulas:

[0141] For example, the cross-linking moiety is represented by one of the following structural formulas: For example, the cross-linking moiety is represented by the following structural formula:

[0142] For example, the cross-linking moiety is represented by the following structural formula: For example, R 5 is H. For example, R 5 is -SO3H. The remaining features and exemplary features of the sixteenth aspect are as described above with respect to the first to fifteenth aspects of the first embodiment.

[0143] In a seventeenth aspect of the first embodiment, the cross-linked polysulfonated polymer comprises sPPS or sPSU, and the cross-linked portion is represented by one of the following structural formulas: For example, the cross-linked polysulfonated polymer comprises sPPS, and the cross-linked portion is represented by one of the following structural formulas: For example, the cross-linked polysulfonated polymer comprises sPPS, and the cross-linked portion is represented by the following structural formula: For example, the cross-linked polysulfonated polymer comprises sPPS, and the cross-linked portion is represented by one of the following structural formulas:

[0144] For example, the cross-linked polysulfonated polymer comprises sPPS, and the cross-linked portion is represented by the following structural formula: The remaining features and exemplary features of the seventeenth aspect are as described above with respect to the first to sixteenth aspects of the first embodiment.

[0145] In an eighteenth aspect of the first embodiment, the cross-linked polysulfonated polymer comprises an average of about 0.5 to about 6 sulfonic acid, sulfonate / ester, and sulfonamide groups per repeating unit. For example, the cross-linked polysulfonated polymer comprises an average of about 0.5 to about 2, about 1 to about 3, about 1.5 to about 2.5, about 2 to about 4, about 1.5 to about 3, or about 2 to about 1.5 sulfonic acid, sulfonate / ester, and sulfonamide groups per repeating unit. For example, the cross-linked polysulfonated polymer comprises an average of about 0.5, about 1, about 1.5, about 2.0, about 2.5, or about 3 sulfonic acid, sulfonate / ester, and sulfonamide groups per repeating unit. The remaining features and exemplary features of the eighteenth aspect are as described above for the first to seventeenth aspects of the first embodiment.

[0146] In a nineteenth aspect of the first embodiment, the cross-linked polysulfonated polymer has a degree of cross-linking of about 10% to about 95%. For example, the cross-linked polysulfonated polymer has a degree of cross-linking of about 15% to about 90%, about 20% to about 80%, about 20% to about 70%, about 20% to about 60%, about 20% to about 50%, about 20% to about 45%, about 20% to about 40%, about 30% to about 50%, about 25% to about 30%, or about 30% to about 35%. For example, the cross-linked polysulfonated polymer has a degree of cross-linking of about 10%, about 15%, about 20%, about 25%, about 30%, about 35%, about 40%, about 45%, about 50%, about 55%, about 60%, about 65%, about 70%, about 75%, about 80%, about 85%, about 90% or about 95%. The remaining features and exemplary features of the nineteenth aspect are as described above with respect to the first to eighteenth aspects of the first embodiment.

[0147] In a twentieth aspect of the first embodiment, the membrane is unsupported, the cross-linked polysulfonated polymer is sPPS, and the cross-linked portion is represented by the following structural formula: The remaining features and exemplary features of the twentieth aspect are as described above with respect to the first to nineteenth aspects of the first embodiment.

[0148] In a twenty-first aspect of the first embodiment, the membrane is unsupported, the cross-linked polysulfonated polymer is sPPS, and the cross-linked portion is represented by one of the following structural formulas: The remaining features and exemplary features of the twenty-first aspect are as described above with respect to the first to twentieth aspects of the first embodiment.

[0149] In a twenty-second aspect of the first embodiment, the PFSA is a polymer comprising a repeating unit represented by structural formula (I): wherein x is an integer between 5 and 14, m is 1 or 2, and n is 2 or 3; and the cross-linked polysulfonated polymer comprises sPPS or sPSU, and the cross-linked portion is represented by one of the following structural formulas: The remaining features and exemplary features of the twenty-second aspect are as described above with respect to the first to twenty-first aspects of the first embodiment.

[0150] In a twenty-third aspect of the first embodiment, the membrane is unsupported and the PFSA is a polymer comprising a repeating unit represented by structural formula (I): wherein x is an integer between 5 and 14, m is 1 or 2, and n is 2 or 3; and further wherein the cross-linked polysulfonated polymer is sPPS, and the cross-linked portion is represented by the following structural formula: The sulfonation degree of sPPS is about 200%, the crosslinking degree of sPPS is about 40%, and the thickness of the second layer is about 0.5 μm to about 2 μm. The remaining features and exemplary features of the twenty-third aspect are as described above with respect to the first to twenty-second aspects of the first embodiment.

[0151] In a twenty-fourth aspect of the first embodiment, the membrane is unsupported and the PFSA is a polymer comprising a repeating unit represented by structural formula (I): wherein x is an integer between 5 and 14, m is 1 or 2, and n is 2 or 3; and further wherein the cross-linked polysulfonated polymer is sPPS, and the cross-linked portion is represented by the following structural formula: The cross-linked portion is represented by one of the following structural formulas: The sulfonation degree of sPPS is about 200%, the crosslinking degree of sPPS is about 25% to about 30%, and the thickness of the second layer is about 1 μm to about 2 μm. The remaining features and exemplary features of the twenty-fourth aspect are as described above with respect to the first to twenty-third aspects of the first embodiment.

[0152] In a twenty-fifth aspect of the first embodiment, the first layer comprises a porous matrix, the porous matrix comprises a matrix polymer, the PFSA and the matrix polymer form an interpenetrating network, and the cross-linked polysulfonated polymer comprises sPPS or sPSU. For example, the cross-linked polysulfonated polymer is sPPS. For example, sPPS comprises a cross-linked portion represented by one of the following structural formulas: For example, the cross-linking moiety is represented by one of the following structural formulas: For example, the cross-linking moiety is represented by the following structural formula: The remaining features and exemplary features of the twenty-fifth aspect are as described above with respect to the first to twenty-fourth aspects of the first embodiment.

[0153] In a second embodiment, the present invention is a method of making a double-layer polyelectrolyte membrane as described herein with respect to the first embodiment and various aspects thereof, the method comprising:

[0154] a) providing a first layer having a first side, and a solution or suspension comprising a polysulfonated polymer and a cross-linking agent,

[0155] b) coating a first side of the first layer with the solution or suspension, thereby producing a coated first layer;

[0156] c) exposing the coated first layer to conditions sufficient to cause a cross-linking reaction between the polysulfonated polymer and the cross-linking agent, thereby producing a bilayer polyelectrolyte membrane.

[0157] In the first aspect of the second embodiment, the cross-linking agent is selected from a polyol, an amine, an epoxide, a thiol or a compound comprising a terminal olefin or an alkyne. For example, the cross-linking agent is selected from glycerol, ethylene glycol, hydroquinone, 2,5-dihydroxybenzene sulfonic acid, 2,5-dihydroxybenzene-1,4-disulfonic acid, biphenyl, tetraglycidylbis(p-aminophenyl)methane, phenylenediamine, 4,4'-thiobisbenzenethiol and tetrafluorostyrene. For example, the cross-linking agent is glycerol, ethylene glycol, hydroquinone or 2,5-dihydroxybenzene sulfonic acid. For example, the cross-linking agent is a polyol, such as glycerol or ethylene glycol. For example, the cross-linking agent is hydroquinone or 2,5-dihydroxybenzene sulfonic acid. The cross-linking agent can be selected from glycerol, ethylene glycol, tetraglycidylbis(p-aminophenyl)methane, phenylenediamine, 4,4'-thiobisbenzenethiol and tetrafluorostyrene.

[0158] In a second aspect of the second embodiment, the conditions sufficient to cause the polysulfonated polymer and the crosslinking agent to undergo a crosslinking reaction include heating the coated first layer to a crosslinking temperature of about 150° C. to about 200° C. for a crosslinking time of about 2 hours to about 96 hours. For example, the crosslinking temperature is about 150° C., about 160° C., about 170° C., about 180° C., about 190° C., or about 200° C. For example, the crosslinking temperature is about 180° C. and the crosslinking time is about 4 hours. For example, the crosslinking time is about 2 hours, about 3 hours, about 4 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours, about 9 hours, about 10 hours, about 20 hours, about 30 hours, about 40 hours, about 50 hours, about 60 hours, about 70 hours, about 80 hours, or about 90 hours. For example, the crosslinking time is about 4 hours. The remaining features and exemplary features of the second aspect are as described above with respect to the first aspect of the second embodiment.

[0159] In a second aspect of the second embodiment, coating the first side of the first layer with the first solution or suspension comprises spraying the first side of the first layer with the first solution or suspension. Alternatively, coating the first side of the first layer with the first solution or suspension comprises dip coating, spin coating, or flow coating the first side of the first layer with the first solution or suspension. The remaining features and exemplary features of the third aspect are as described above with respect to the first and second aspects of the second embodiment.

[0160] In a third embodiment, the present invention is a membrane electrode assembly (MEA) comprising: a double-layer polyelectrolyte membrane as described herein with respect to the first embodiment and its various aspects; a cathode; and an anode, wherein the double-layer electrolyte membrane is disposed between the anode and the cathode.

[0161] In a first aspect of the third embodiment, the cathode is disposed on the first layer of the double-layer electrolyte membrane and the anode is disposed on the second layer of the double-layer electrolyte membrane. Alternatively, the anode is disposed on the first layer of the double-layer electrolyte membrane and the cathode is disposed on the second layer of the double-layer electrolyte membrane.

[0162] In a fourth embodiment, the invention is a fuel cell comprising one or more MEAs described herein with respect to the third embodiment and various aspects thereof and one or more gas flow bipolar plates.

[0163] In various embodiments, the present invention is

[0164] 1. A double-layer polyelectrolyte membrane, the double-layer polyelectrolyte membrane comprising a first layer and a second layer, wherein:

[0165] The first layer comprises perfluorosulfonic acid (PFSA), and

[0166] The second layer comprises a cross-linked polysulfonated polymer, wherein the cross-linked polysulfonated polymer comprises a sulfonated polyphenylsulfone (sPPS), a sulfonated polyetheretherketone (sPEEK), a sulfonated polyphosphazene (sPOP), a sulfonated polybenzimidazole (sPBI), a sulfonated polyethersulfone (sPES), a sulfonated polyphenylene oxide (sPPO), a sulfonated polyaryletherketone (sPAEK), a sulfonated polysulfone, a sulfonated polysulfide sulfone, a sulfonated polyimide (sPI), a sulfonated polyetherimide (sPEI), a sulfonated polyamine, or a combination thereof,

[0167] And wherein the first layer is disposed on the second layer.

[0168] 2. The double-layer polyelectrolyte membrane according to claim 1, wherein the PFSA is a polymer comprising a repeating unit represented by structural formula (I):

[0169]

[0170] in

[0171] x is an integer between 1 and 15,

[0172] m is an integer between 0 and 2,

[0173] n is an integer between 1 and 5, and

[0174] Represents the point of attachment to the adjacent repeat unit.

[0175] 3. The double-layer polyelectrolyte membrane according to claim 2, wherein

[0176] x is an integer between 5 and 14,

[0177] m is 1 or 2, and

[0178] n is 2 or 3.

[0179] 4. The double-layer polyelectrolyte membrane according to claim 2 or 3, wherein the PFSA is a polymer comprising about 900 to about 1100 repeating units represented by structural formula (I).

[0180] 5. The double-layer polyelectrolyte membrane according to any one of claims 1 to 4, wherein the cross-linked polysulfonated polymer comprises sPPS, sPEEK, sPOP or sPBI.

[0181] The double-layer polyelectrolyte membrane according to claim 5 , wherein the cross-linked polysulfonated polymer comprises sPPS.

[0182] 7. The double-layer polyelectrolyte membrane according to any one of claims 1 to 6, wherein the cross-linked polysulfonated polymer comprises a cross-linking portion represented by one of the following structural formulas:

[0183]

[0184] in

[0185] R 1 , R 2 , R 3 and R 4 Each of which is independently selected from H, C 1-12 Alkyl, C 1-12 Haloalkyl, C 6-14 Aryl and C 6-14 Aryl (C 1-12 Alkylene);

[0186] M 2+ Selected from Mr. 2+ , Ca 2+ , Ba 2+ and Al(X) 2+, wherein X is a halogen, acetate or nitrate; and

[0187] represents the point of attachment of the cross-linking moiety to the repeating unit of the cross-linked polysulfonated polymer.

[0188] 8. The double-layer polyelectrolyte membrane according to claim 7, wherein the cross-linked portion is represented by one of the following structural formulas:

[0189]

[0190] 9. The double-layer polyelectrolyte membrane according to claim 7, wherein the cross-linked portion is represented by one of the following structural formulas:

[0191]

[0192] 10. The double-layer polyelectrolyte membrane according to any one of claims 1 to 9, wherein the first layer further comprises a porous matrix, the porous matrix comprising a matrix polymer, and wherein the PFSA and the matrix polymer form an interpenetrating network.

[0193] 11. The double-layer polyelectrolyte membrane of claim 10, wherein the first layer comprises about 70 wt% to about 99 wt% PFSA.

[0194] 12. The double-layer polyelectrolyte membrane of claim 10, wherein the first layer comprises about 78 wt% to about 95 wt% PFSA.

[0195] 13. The double-layer polyelectrolyte membrane according to any one of claims 10 to 12, wherein the matrix polymer is polytetrafluoroethylene (PTFE).

[0196] 14. The double-layer polyelectrolyte membrane of claim 13, wherein the matrix polymer is expanded polytetrafluoroethylene (ePTFE).

[0197] 15. The double-layer polyelectrolyte membrane of any one of claims 1 to 14, wherein the degree of sulfonation of the cross-linked polysulfonated polymer is from about 20% to about 100%.

[0198] 16. The double-layer polyelectrolyte membrane of claim 15, wherein the cross-linked polysulfonated polymer has a degree of sulfonation of about 40% to about 80%.

[0199] 17. The double-layer polyelectrolyte membrane of claim 15, wherein the cross-linked polysulfonated polymer has a degree of sulfonation of about 50% to about 60%.

[0200] 18. The double-layer polyelectrolyte membrane of any one of claims 1 to 17, wherein the cross-linked polysulfonated polymer has a gel fraction of about 50% to about 100%.

[0201] 19. The double-layer polyelectrolyte membrane of any one of claims 1-18, wherein the thickness of the first layer is from about 5 μm to about 175 μm.

[0202] 20. The double-layer polyelectrolyte membrane of any one of claims 1-19, wherein the thickness of the second layer is from about 0.2 μm to about 170 μm.

[0203] 21. The double-layer polyelectrolyte membrane of claim 20, wherein the second layer has a thickness of about 0.2 μm to about 10 μm.

[0204] 22. The double-layer polyelectrolyte membrane of any one of claims 1-21, wherein the first layer is continuous.

[0205] 23. A double-layer polyelectrolyte membrane according to any one of claims 1 to 22, wherein the membrane is unsupported.

[0206] 24. The double-layer polyelectrolyte membrane according to claim 1, wherein:

[0207] The PFSA is a polymer comprising repeating units represented by structural formula (I):

[0208]

[0209] in

[0210] x is an integer between 5 and 14,

[0211] m is 1 or 2, and

[0212] n is 2 or 3; and

[0213] The cross-linked polysulfonated polymer comprises sPPS, and the cross-linked portion is represented by one of the following structural formulas:

[0214]

[0215] 25. The double-layer polyelectrolyte membrane according to claim 1, wherein:

[0216] The first layer comprises a porous matrix, the porous matrix comprising a matrix polymer, and wherein the PFSA and the matrix polymer form an interpenetrating network;

[0217] The PFSA is a polymer comprising repeating units represented by structural formula (I):

[0218]

[0219] in

[0220] x is an integer between 5 and 14,

[0221] m is 1 or 2, and

[0222] n is 2 or 3;

[0223] The matrix polymer comprises ePTFE; and

[0224] The cross-linked polysulfonated polymer comprises sPPS, and the cross-linked portion is represented by one of the following structural formulas:

[0225]

[0226] 26. A method for manufacturing a double-layer polyelectrolyte membrane according to any one of claims 1 to 25, the method comprising:

[0227] a) providing a first layer having a first side, and a solution or suspension comprising a polysulfonated polymer and a cross-linking agent,

[0228] b) coating said first side of said first layer with said solution or suspension, thereby producing a coated first layer;

[0229] c) exposing the coated first layer to conditions sufficient to cause a cross-linking reaction between the polysulfonated polymer and the cross-linking agent, thereby producing the bilayer polyelectrolyte membrane.

[0230] 27. The method of claim 26, wherein the cross-linking agent is selected from a polyol, an amine, an epoxide, a thiol, or a compound containing a terminal olefin or an alkyne.

[0231] 28. The method of claim 26, wherein the cross-linking agent is selected from the group consisting of glycerol, ethylene glycol, tetraglycidylbis(p-aminophenyl)methane, phenylenediamine, 4,4'-thiobisbenzenethiol, and tetrafluorostyrene.

[0232] 29. The method of claim 26, wherein the cross-linking agent is a polyol.

[0233] 30. The method of claim 29, wherein the cross-linking agent is ethylene glycol or glycerol.

[0234] 31. The method of any one of claims 26-30, wherein the conditions sufficient to cause the polysulfonated polymer and the cross-linking agent to undergo a cross-linking reaction comprise heating the coated first layer to a cross-linking temperature of about 150°C to about 200°C for a cross-linking time of about 2 hours to about 96 hours.

[0235] 32. The method of claim 31, wherein the cross-linking temperature is about 180°C.

[0236] 33. The method of claim 31, wherein the cross-linking time is about 4 hours.

[0237] 34. The method of any one of claims 26-33, wherein coating the first side of the first layer with the first solution or suspension comprises spraying the first side of the first layer with the first solution or suspension.

[0238] 35. A membrane electrode assembly (MEA), comprising:

[0239] A double-layer polyelectrolyte membrane according to any one of claims 1 to 25;

[0240] cathode; and

[0241] anode,

[0242] The double-layer electrolyte membrane is disposed between the anode and the cathode.

[0243] 36 . The MEA according to claim 35 , wherein the cathode is disposed on the first layer of the double-layer electrolyte membrane, and the anode is disposed on the second layer of the double-layer electrolyte membrane.

[0244] 37. The MEA according to claim 35, wherein the anode is disposed on the first layer of the double-layer electrolyte membrane, and the cathode is disposed on the second layer of the double-layer electrolyte membrane.

[0245] 38. A fuel cell comprising one or more MEAs according to any one of claims 35 to 37 and one or more airflow bipolar plates.

[0246] Example

[0247] Material

[0248] PPS (Solvay Radel R-5000, MW=5000) was purchased from Solvay. Sulfuric acid (H2SO4) was purchased from Sigma-Aldrich (95-98%, CAS 7664-93-9). Ethylene glycol was purchased from Sigma-Aldrich (≥99%, CAS107-21-1). 211 PFSA membrane (NR-211) was purchased from Fuel Cell Store.

[0249] Example 1. Sulfonation of PPS.

[0250] General Procedure: PPS is sulfonated by reacting the polymer with H2SO4. PPS is dissolved in concentrated H2SO4 at a concentration of 25 mg / mL and stirred at 60-70°C for 10-48 hours. The sulfonated polymer is precipitated by adding the reaction mixture dropwise into H2O at 0°C. The resulting precipitated polymer is centrifuged and separated. The sulfonated PPS (sPPS) is redispersed in H2O at room temperature and washed using dialysis until a neutral pH is recorded. The washed sPPS is dried on a hot plate to provide the final product. The degree of sulfonation of the sPPS can be adjusted by adjusting the reaction time (1-72 hours).

[0251] Example Synthesis: PPS (Radel-5000NT) was sulfonated by reacting the polymer with H2SO4. PPS resin was ground into powder using an industrial grinder. PPS powder (20 g) was dissolved in concentrated H2SO4 at a concentration of 25 mg / mL and stirred at 60°C for 8 hours. The resulting sulfonated polymer was precipitated by adding the reaction mixture dropwise to H2O at 0°C. The resulting precipitated polymer was centrifuged and separated. The sulfonated PPS (sPPS) was redispersed in H2O at room temperature and washed using dialysis until a neutral pH was recorded. The washed sPPS was dried on a hot plate to provide the final product. The reaction yield by mass was measured to be 91%. The titration of the resulting product determined the IEC to be 3.605 meq / g (corresponding to 2.0 sulfonic acids per repeating unit), as measured according to the procedure described in Example 3.

[0252] The sulfonated polymers were measured at a concentration of about 10 wt % in DMSO-d6. 1 H NMR was used to confirm the polymer structure and degree of sulfonation. A 500 MHz Bruker Ultrashield 500Plus spectrometer was used to acquire 1 H NMR spectra were processed using SpinWorks 4. A pulse angle of 30° and a pulse delay of 5 s were used. 1 H NMR experiments were performed with 32 scans. 1 H NMR spectrum Fig.16 The number and position of the sulfonic acid groups in the repeating unit were determined using the integration of the peaks as shown in Table 1 below. Fig.16 as shown in .

[0253] Table 1. sPPS 1 H NMR peak integration, 1 H NMR IEC values ​​and IEC values ​​determined by titration.

[0254]

[0255] Peak integration and normalization by setting the peak integration of peak B to value "4", which is the number of protons at the B site of each repeating unit (Table 1). The identity of peak B is based on the presence of sulfone bond to provide space and electronic protection to the B site and is free from sulfonation. The number of sulfonic acid moieties of each repeating unit is calculated by the ratio of peak integration to peak C. In addition, the IEC value is calculated as follows based on the peak integration value. The value of IEC is related to the material weight of each sulfonic acid moiety. This is referred to as effective weight (EW). Since the sPPS prepared has a single polymer skeleton, the sulfonic acid of each repeating unit is calculated using the ratio of C peak integration (which matches the number of sulfonic acid groups in the structure) to any hydrogen peak, using the following formula:

[0256]

[0257] The number of sulfonic acid moieties per repeating unit was converted to EW according to the following formula:

[0258]

[0259] Among them, MW RU is the molecular weight of the repeating unit (400 g / mol for PPS), is the molecular weight of the sulfonic acid portion (82 g / mol). EW is then converted to IEC as follows:

[0260]

[0261] Based on sPPS 1 The IEC numbers obtained for each integrated peak in the H NMR spectrum and the average numbers are in good agreement with the experimental IEC values ​​obtained by titration (see Table 1). This agreement indicates that there are no other significant sulfonation positions on the repeating unit and that sPPS contains two sulfonic acid moieties per repeating unit, which are located on the biphenyl portion of the backbone, such as Fig.16 as shown in .

[0262] Example 2. Casting of freestanding sPPS membranes.

[0263] A solution of 1-5 wt% sPPS in an ethylene glycol: water mixture was added to a Kapton cell. The solution was allowed to dry overnight. The dried sPPS film was crosslinked by condensation reaction with the residual ethylene glycol by heating to 180°C under flowing nitrogen for 4 hours to obtain a water-stable sPPS polymer film.

[0264] Example 3. Determination of ion exchange capacity and degree of crosslinking.

[0265] The ion exchange capacity (IEC) of sPPS polymer and cross-linked sPPS membrane was measured by titration. A piece of polymer or membrane was dried in an oven under flowing nitrogen at 100 °C for 12 hours and then weighed to determine the mass of the material (W dry ). The dried material was soaked in 20 mL 2M NaCl for 30 min, and then 10 μL phenolphthalein was added. Standardized NaOH solution (C NaOH ,0.01M) until the solution turns light pink. Record the volume of NaOH solution added (V NaOH ). Then calculate IEC as follows:

[0266]

[0267] The degree of crosslinking (%) is defined as the fraction of sulfonic acid moieties that react with the crosslinker molecules. The degree of crosslinking is calculated as follows:

[0268]

[0269] Example 4. Conductivity measurements of freestanding membranes.

[0270] The membrane conductivity was measured using a Scribner Bekktech BT-112 HT conductivity cell with an Admiral Squidstat potentiostat in 4-point probe geometry. The conductivity was evaluated by current measurements during linear sweep voltammetry from -0.5 V to 0.5 V. The conductivity was then calculated from the current-voltage slope and sample thickness.

[0271] After cross-linking of the sPPS material, the loss of proton concentration leads to a nonlinear decrease in membrane conductivity. The relationship between conductivity and cross-linking degree is shown in Fig. 9 Shown in.

[0272] Example 5. Spraying with sPPS and ethylene glycol as crosslinking agents membrane.

[0273] The sPPS was deposited onto the The spray solution consisted of 0.5 wt% or 0.75 wt% sPPS in H2O and different amounts of crosslinker (ethylene glycol or glycerol). In the case of ethylene glycol, 6 ethylene glycol molecules were added to each repeating unit of the polymer. The solution was stirred for 30-60 minutes before use. The membrane substrate was kept under vacuum. The following parameters were used for spraying: power 0.8-1.3 W, nozzle height 40 mm, temperature 60 ° C, flow rate 0.25-0.5 mL / min. The number of polymer layers was adjusted for the desired coating thickness. 75 layers were deposited to obtain a sPPS coating with a thickness of 1.5 μm, and 38 layers were deposited to obtain a thickness of 0.75 μm. The following ranges can be used for spraying parameters: sPPS solution concentration: 0.05-20 wt%; substrate temperature: 5-200 ° C; nozzle height: 10-70 mm; flow rate: 0.1-4 mL / min; power: 0.8-5 W; cross-linking amount (specific to ethylene glycol and glycerol): 0.2-12 molecules per repeating unit of sPPS.

[0274] Example 6. Cross-linking sPPS coating on membrane.

[0275] Use ethylene glycol or glycerol to crosslink sPPS coating on the membrane. For cross-linking, the sPPS-coated The film was heated to 180°C under flowing nitrogen while taped to an aluminum mask under tension for 4 hours or heated to 180°C in a series of temperature steps over 4 days to obtain a water-stable sPPS polymer coating. The resulting coating had a crosslinking degree of 30-50%.

[0276] Example 7. Preparation of membrane electrode assembly.

[0277] The membrane electrode assembly (MEA) uses a double-layer polyelectrolyte membrane and a 5 cm 2 For MEA fabrication, a 3-inch x 3-inch membrane was placed between two gas diffusion electrodes (GDEs) on Sigracet 22BB with 0.2 mg Pt / cm 2 (20% Pt on Vulcan carbon), each with an area of ​​5 cm 2 The GDE has a pre-deposited catalyst layer on one side of the microporous layer and is implemented so that the catalyst layer interfaces with the membrane. A 5 cm 2 A 3" x 3" PTFE gasket for the window was used to surround the gas diffusion electrode to prevent reactant gas leakage. The gasket thickness was adjusted to allow 80% compression of the GDE when the MEA was fastened between two fuel cell end plates.

[0278] Example 8. Testing of double-layer polyelectrolyte membranes in fuel cells.

[0279] Membrane performance in fuel cells was evaluated via H2 permeation measurements, fuel cell polarization curves, and accelerated stress testing.

[0280] H2 permeation measurement

[0281] The H2 permeation was measured by performing cyclic voltammetry, where the cathode side electrode was scanned between 0.1 V and 0.8 V at a voltage scan rate of 2 mV / s at 80°C and 100% RH, with a H2 flow rate of 0.4 lpm on the anode side and an Ar flow rate of 0.4 lpm on the cathode side, with no back pressure. The fuel cell polarization curves were measured by performing constant voltage measurements: from open circuit potential to 0.3 V and back to open circuit potential at 80°C at different RH values, with an increment of 0.5 V between open circuit potential and 0.7 V, and an increment of 1 V between 0.7 V and 0.3 V, with a H2 flow rate of 0.2 lpm on the anode side and an air or O2 flow rate of 0.2 lpm on the cathode side, and a back pressure of 50 kPa. g The data obtained in Figure 4 and 10 The membrane studied was coated with sPPS with a cross-linking degree of 40%. The data showed that the hydrogen permeation increased from 1.33 mA / cm 2 (0μm coating) changes to 1.05mA / cm 2 (0.75μm coating) to 0.84mA / cm 2 (1.5 μm coating), thus indicating that the low gas permeability coating reduces the permeation of hydrogen through the PFSA-based membrane.

[0282] Electrochemical impedance spectroscopy

[0283] In H2 pump mode, 150 mA / cm 2 and 75mA / cm 2 The excitation amplitude was used for electrochemical impedance spectroscopy measurements. The measurements were performed at 80°C and 100% RH with a H2 flow rate of 0.05 lpm on the anode side and an Ar flow rate of 0.05 lpm on the cathode side, without back pressure.

[0284] Fig.15 The data in the study surprisingly showed that In the bilayer film of 211 and cross-linked sPPS, sPPS and The layers show no contact resistance between each other, which means that protons encounter no additional resistance when moving between the layers. Contact resistance between heterogeneous materials is frequently observed in conductive systems and constitutes a significant obstacle for layered geometries. Therefore, a bilayer system comprising two materials stacked on top of each other is expected to show a decrease in ionic conductivity due to the interface / contact resistance. To evaluate the contact resistance in bilayer membranes, a 25 μm 211 film, 1.5 μm 40% cross-linked sPPS film and double-layer film (25 μm Surprisingly, the ASR of the two-layer system is almost equal to the sum of the ASR values ​​of the individual layers.

[0285] Accelerated Stress Test (AST)

[0286] AST is performed according to one of the following protocols:

[0287] Protocol A: AST included an aggressive strenuous phase and a periodic hydration phase, each lasting up to 4.5 hours and 0.5 hours, respectively. During the aggressive strenuous phase, the cell was set to 110°C, with a H2 flow of 0.1 lpm on the anode, an O2 flow of 0.1 lpm on the cathode, no back pressure, and both gases at 30% RH. During the hydration phase, the cell was set to 80°C, with a H2 flow of 0.1 lpm on the anode, an O2 flow of 0.1 lpm on the cathode, no back pressure, and both gases at 100% RH. The results of the test are shown in Figure 6 Shown in.

[0288] Protocol B: AST was performed by applying RH cycling where the gas was switched between 0 and 100% RH at 2-minute intervals while keeping the cell in open circuit. The cell was maintained at 90°C with 0.1 lpm H2 flow on the anode and 0.1 lpm air flow on the cathode with no back pressure. During the accelerated stress test, H2 permeation was measured periodically and wastewater was collected. The results of the test are given in Fig.11 and 12 Shown in.

[0289] Fig.11 The data in Figure 2 show that as the thickness of the cross-linked sPPS coating increases, The 211 films showed improved durability. When compared to the change in overall film thickness, the increase in durability was found to be disproportionately greater at thicker coatings. Specifically, the 211 films with a 1.5 μm 40% cross-linked sPPS coating 211(25μm) is only 211 is 6% thicker but withstands the test conditions longer than 211 is 3 times longer.

[0290] Fig.12 The data in confirm that the thicker cross-linked sPPS coating (40% cross-linking degree) The 211 membranes exhibit significantly higher durability. In addition, the increase in H2 permeation at the end of the service life for the membranes with thicker coatings occurs significantly more gradually, compared to the rapid deterioration of hydrogen permeation in membranes with thinner coatings or no coating. The gradual membrane deterioration near the end of the service life observed in membranes with thicker coatings is unexpected and enables the safety features of hydrogen devices to be improved to prevent catastrophic degradation at the end of the service life.

[0291] Fig.12 The data also show that compared with the single layer Compared with the 211 membrane and the cross-linked sPPS membrane itself, The double-layer membrane with 211 and cross-linked sPPS coating is more durable. The fuel cell durability of the cross-linked sPPS membrane is less than 100 hours (see, for example, Kim JD et al., "Chemically Crosslinked Sulfonated Polyphenylsulfone (CSPPSU) Membranes for PEM Fuel Cells," Membranes, 10 (2): 31 (2020)). Similarly, 211 showed significantly less than 100 hours of AST durability ( Fig.12 ). Unexpectedly, including The bilayer film of 211 base layer and 1.5 μm 40% cross-linked sPPS coating showed significantly longer durability than either component material by at least 3 times ( Fig.12 ).

[0292] Example 9. Evaluation of water stability of cross-linked sPPS membranes.

[0293] The water stability of the coating material before and after cross-linking was evaluated by cyclically drying the membrane at 80°C for 12 hours and collecting its mass, and then immersing it in refluxing water for 20-25 hours. The as-synthesized sPPS freestanding membrane is highly soluble in water. The non-crosslinked sPPS membrane immersed in boiling water quickly and completely dissolved. After the ethylene glycol cross-linking procedure, the 40% cross-linked sPPS freestanding membrane showed excellent boiling water stability, with a weight loss of less than 3% after 120 hours. The results of the test are shown in Figure 8 Shown in.

[0294] Example 10. Testing of coated PFSA membranes comprising various PFSA layers.

[0295] PFSA base membranes (supported) of varying thickness from multiple suppliers with cross-linked sPPS coatings (1.5 μm coating, 40% cross-linking) were examined. (20 μm thickness) and 211 (25 μm thickness)). When operated in a single-cell fuel cell, the coated membrane exhibited full functionality as a proton exchange membrane (see Fig.13 In addition, the hydrogen permeation of the coated membranes was greatly reduced compared to the uncoated baseline ( Fig.14 ). The data show that the method of coating a PFSA layer with a layer of a cross-linked sulfonated polymer is applicable to all major commercially available PFSA-based membranes and enables a significant increase in fuel cell power density while reducing hydrogen permeation.

[0296] Example 11. Evaluation of swelling and delamination in films.

[0297] The dimensional stability of the film was evaluated by measuring the size and thickness of the film using a ruler and a micrometer, soaking it in 80°C water for 1 hour, and measuring its size and thickness again after the 80°C water soak. 211 exhibited a substantially different degree of swelling in 80°C water (28-33%) than free-standing 40% cross-linked sPPS (147-209%), free-standing 90% cross-linked sPSU (0%), and free-standing 90% cross-linked sPPO (8%). The large difference in material swelling would be expected to result in significant delamination of the layers in a coated two-layer system. However, the 1.5 μm polysulfonated polymer layer and the 25 μm The 211-layer bilayer film did not delaminate after exposure to water at 80°C for 1 hour. The swelling properties of the 211 membrane for sPPS and sPSU were very similar (see Table 2). In addition, no evidence of double layer delamination was found during AST evaluations in which the membranes were cyclically hydrated and dehydrated.

[0298] Table 2. 211, 40% cross-linked sPPS and Swelling values ​​of a double-layer film on 211 containing a 1.5 μm thick cross-linked sPPS coating.

[0299]

[0300] Without wishing to be bound by any particular theory, it is believed that the claimed polymers of the present disclosure exhibit unexpected performance in bilayer membranes because the polymer backbone comprises moieties having nucleophilic lone pairs of electrons and moieties having electrophilic aromatic rings. The nucleophilic lone pairs of electrons exhibit electrostatic attraction to protons on the sulfonic acid moieties on the surface of the PFSA, while the electrophilic aromatic rings exhibit electrostatic attraction to the deprotonated sulfonic acid moieties (sulfonate / ester moieties) on the surface of the PFSA. In a representative number of the claimed polymers, these electrostatic interactions surprisingly proved to be sufficient to overcome the mechanical forces generated by the significantly mismatched expansion between the layers, thereby preventing delamination of the layers.

[0301] Example 12. Preparation of a sPPS coated with hydroquinone cross-linked 211 layers of double-layer film

[0302] Spraying with sPPS and hydroquinone solution membrane.

[0303] The sPPS was deposited onto the The spray solution was prepared with 0.75 wt% sPPS and 0.19 wt% hydroquinone in H2O (1.3 hydroquinone molecules per sPPS repeating unit). The solution was stirred for 30-60 minutes before use. The membrane substrate was kept under vacuum. The following parameters were used for spraying: power 0.8-1.3 W, nozzle height 40 mm, temperature 60 ° C, flow rate 0.25-0.5 mL / min. The number of polymer layers was adjusted for the desired coating thickness. 75 layers were deposited to obtain a sPPS coating of 1.5 μm thickness. The following ranges can be used for spraying parameters: sPPS solution concentration: 0.05-15 wt %; substrate temperature: 20-200 ° C; nozzle height: 10-70 mm; flow rate: 0.1-4 mL / min; power: 0.8-5 W; cross-linking dosage: 0.1-4 molecules per repeating unit of sPPS.

[0304] Cross-linking sPPS coating on membrane.

[0305] Using hydroquinone cross-linking sPPS coating on the membrane. For cross-linking, the sPPS-coated The film was heated to 200°C under flowing nitrogen for 2 hours while taped under tension to an aluminum mask to obtain a water-stable sPPS polymer coating. The resulting coating was 25-30% cross-linked.

[0306] Example 13. Preparation of a sPPS coated with sPPS cross-linked with 2,5-dihydroxybenzenesulfonic acid 211 layers of double-layer film

[0307] Spraying with sPPS and 2,5-dihydroxybenzenesulfonic acid solution membrane.

[0308] The sPPS was deposited onto the The spray solution was prepared with 0.75 wt% sPPS and 0.39 wt% potassium salt of 2,5-dihydroxybenzenesulfonic acid (1.3 potassium salt molecules of 2,5-dihydroxybenzenesulfonic acid per sPPS repeating unit) in H2O. The solution was stirred for 30-60 minutes before use. The membrane substrate was kept under vacuum. The following parameters were used for spraying: power 0.8-1.3 W, nozzle height 40 mm, temperature 60 ° C, flow rate 0.25-0.5 mL / min. The number of polymer layers was adjusted for the desired coating thickness. 75 layers were deposited to obtain a sPPS coating of 1.5 μm thickness. The following ranges can be used for spraying parameters: sPPS solution concentration: 0.05-15 wt %; substrate temperature: 20-200 ° C; nozzle height: 10-70 mm; flow rate: 0.1-4 mL / min; power: 0.8-5 W; cross-linking dosage: 0.1-4 molecules per repeating unit of sPPS.

[0309] Cross-linking sPPS coating on membrane.

[0310] The potassium salt of 2,5-dihydroxybenzenesulfonic acid was used to crosslink sPPS coating on the membrane. For cross-linking, the sPPS-coated The film was heated to 200°C under flowing nitrogen for 2 hours while taped under tension to an aluminum mask to obtain a water-stable sPPS polymer coating. The resulting coating was 25-30% cross-linked.

[0311] Acidification of sPPS cross-linked with 2,5-dihydroxybenzenesulfonic acid

[0312] The cross-linked membrane was treated with 1 M HCl aqueous solution at 25°C for 1 hour. The membrane was removed from the HCl solution and rinsed with DI water 3-4 times until the outflowing water remained neutral. The membrane was then dried at 25°C.

[0313] Example 14. Preparation of a sPPS coated with biphenyl crosslinked 211 layers of double-layer film

[0314] Spraying with sPPS and biphenyl solution membrane.

[0315] The sPPS was deposited onto the The spray solution was prepared with 0.75 wt% sPPS and 0.2 wt% biphenyl (1 biphenyl molecule per sPPS repeating unit) in ethanol. The solution was stirred for 30-60 minutes before use. The membrane substrate was kept under vacuum. The following parameters were used for spraying: power 0.8-1.3 W, nozzle height 40 mm, temperature 60 ° C, flow rate 0.25-0.5 mL / min. The number of polymer layers was adjusted for the desired coating thickness. 75 layers were deposited to obtain a sPPS coating of 1.5 μm thickness. The following ranges can be used for spraying parameters: sPPS solution concentration: 0.05-15 wt %; substrate temperature: 20-200 ° C; nozzle height: 10-70 mm; flow rate: 0.1-4 mL / min; power: 0.8-5 W; cross-linking dosage: 0.1-4 molecules per repeating unit of sPPS.

[0316] Cross-linking sPPS coating on membrane.

[0317] Use biphenyl cross-linking sPPS coating on the membrane. For cross-linking, the sPPS-coated The film was heated to 200°C under flowing nitrogen for 2 hours while taped under tension to an aluminum mask to obtain a water-stable sPPS polymer coating. The resulting coating was 30-35% cross-linked.

[0318] The properties of sPPS coated films prepared according to Examples 6 and 12-14 using different crosslinking agents were examined. The fuel cell polarization and power curves of 211 show that all membranes examined are fully capable of functioning as proton exchange membranes ( Fig.17 ).

[0319] H2 permeation studies performed according to Example 8 showed that bilayer membranes prepared with sPPS and biphenyl, hydroquinone, and 2,5-dihydroxybenzenesulfonic acid were as effective or better at reducing H2 permeation than sPPS cross-linked with ethylene glycol ( Fig.18 ). Fig.10 As shown in Comparison of H2 permeation in 211 showed a significant improvement in H2 permeation for sPPS-based bilayer membranes cross-linked with all cross-linkers examined.

[0320] Example 15. Preparation of a sPSU coated with hydroquinone cross-linked 211 layers of double-layer film

[0321] Sulfonation of PSU

[0322] Sulfonation of PSU is carried out by reacting the polymer with H2SO4. PSU resin is ground into powder using an industrial grinder. 20 mL of concentrated sulfuric acid is heated to 60°C under mechanical stirring. After the sulfuric acid reaches 60°C, 2 g of ground sPSU is added. After the sPSU is dissolved, the reaction is allowed to proceed at 60°C for 8 hours while stirring. The sulfonated polymer is precipitated by adding the reaction mixture dropwise to H2O at 0°C. The resulting precipitated polymer is centrifuged and separated. The sulfonated PSU (sPSU) is redispersed in H2O at room temperature and washed using dialysis until a neutral pH is recorded. The washed sPPS is dried on a hot plate to provide the final product.

[0323] Spraying with sPSU and hydroquinone solution membrane.

[0324] The sPSU was deposited onto the The spray solution was prepared with 0.75 wt% sPSU and 0.177 wt% hydroquinone in H2O (1.3 hydroquinone molecules per sPSU repeating unit). The solution was stirred for 30-60 minutes before use. The membrane substrate was kept under vacuum. The following parameters were used for spraying: power 0.8-1.3 W, nozzle height 40 mm, temperature 60 ° C, flow rate 0.25-0.5 mL / min. The number of polymer layers was adjusted for the desired coating thickness. 75 layers were deposited to obtain a sPPS coating of 1.5 μm thickness. The following ranges can be used for spraying parameters: sPSU solution concentration: 0.05-15 wt %; substrate temperature: 20-200 ° C; nozzle height: 10-70 mm; flow rate: 0.1-4 mL / min; power: 0.8-5 W; cross-linking dose: 0-4 molecules per repeating unit of sPSU.

[0325] Cross-linking sPSU coating on membrane.

[0326] Using hydroquinone cross-linking sPSU coating on the membrane. For cross-linking, the sPSU-coated The film was heated to 200°C for 2 hours under flowing nitrogen while secured to an aluminum mask with tape under tension to obtain a water-stable sPSU polymer coating. The resulting coating was 90% cross-linked.

[0327] Example 16. Preparation of a sPPO coated with hydroquinone cross-linked 211 layers of double-layer film

[0328] Sulfonation of PPO

[0329] PPO was dissolved in chloroform at a concentration of 100 mg / mL under nitrogen purge. PPO in chloroform was stirred in an ice bath (0°C) for 30 minutes prior to sulfonation. Chlorosulfonic acid was added dropwise at a molar ratio of 1:1 to PPO to the PPO solution. The reaction was allowed to proceed for 30 minutes and then terminated by the addition of DI water. The sulfonated PPO (sPPO) was redispersed in H2O at room temperature and washed using dialysis until a neutral pH was recorded. The washed sPPO was dried on a hot plate to provide the final product.

[0330] Spray with sPPO and hydroquinone solution membrane.

[0331] The sPPO was deposited onto the The spray solution was prepared with 0.75 wt% sPPO and 0.385 wt% or 0.077 wt% hydroquinone (0.5 or 0.1 hydroquinone molecules per sPPO repeating unit) in a 1:1 H2O:ethanol solution. The solution was stirred for 30-60 minutes before use. The membrane substrate was kept under vacuum. The following parameters were used for spraying: power 0.8-1.3 W, nozzle height 40 mm, temperature 60 ° C, flow rate 0.25-0.5 mL / min. The number of polymer layers was adjusted for the desired coating thickness. 75 layers were deposited to obtain a sPPS coating of 1.5 μm thickness. The following ranges can be used for spraying parameters: sPPS solution concentration: 0.05-15 wt %; substrate temperature: 20-200 ° C; nozzle height: 10-70 mm; flow rate: 0.1-4 mL / min; power: 0.8-5 W; crosslinking dosage: 0.05-4 molecules per repeating unit of sPPO.

[0332] Cross-linking sPPO coating on membrane.

[0333] Using hydroquinone cross-linking sPPO coating on the membrane. For cross-linking, the sPPO-coated The film was heated to 200°C for 2 hours under flowing nitrogen while taped under tension to an aluminum mask to obtain a water-stable sPPO polymer coating. The resulting coatings were 20% and 90% cross-linked for 0.1 and 0.5 hydroquinones per repeating unit of sPPO, respectively.

[0334] The properties of bilayer membranes having coatings comprising sPPS, sPSU and sPPO cross-linked with hydroquinone and prepared according to Examples 6, 15 and 16 were examined. Fig.19 The double-layer film and the uncoated 211 fuel cell polarization and power curves.

[0335] Fig. 20 . Data obtained in a H2 permeation study conducted according to Example 8 on a bilayer membrane having a coating comprising sPPS, sPSU and sPPO cross-linked with hydroquinone are shown in FIG.

[0336] The teachings of all patents, published applications, and references cited herein are incorporated by reference in their entirety.

[0337] While the invention has been particularly shown and described with reference to example embodiments thereof, it will be understood by those skilled in the art that various changes in form and details may be made therein without departing from the scope of the invention as encompassed by the appended claims.

Claims

1. A double-layer polyelectrolyte membrane, the double-layer polyelectrolyte membrane comprising a first layer and a second layer, wherein: The first layer comprises perfluorosulfonic acid (PFSA), and The second layer comprises a cross-linked polysulfonated polymer, wherein the cross-linked polysulfonated polymer comprises a sulfonated polyphenylsulfone (sPPS), a sulfonated polyetheretherketone (sPEEK), a sulfonated polyphosphazene (sPOP), a sulfonated polybenzimidazole (sPBI), a sulfonated polyethersulfone (sPES), a sulfonated polyphenylene oxide (sPPO), a sulfonated polyaryletherketone (sPAEK), a sulfonated polysulfone, a sulfonated polysulfide sulfone, a sulfonated polyimide (sPI), a sulfonated polyetherimide (sPEI), a sulfonated polyamine, or a combination thereof, And wherein the first layer is disposed on the second layer.

2. The double-layer polyelectrolyte membrane according to claim 1, wherein the PFSA is a polymer comprising a repeating unit represented by structural formula (I): in x is an integer between 1 and 15, m is an integer between 0 and 2, n is an integer between 1 and 5, and Represents the point of attachment to the adjacent repeat unit.

3. The double-layer polyelectrolyte membrane according to claim 2, wherein x is an integer between 5 and 14, m is 1 or 2, and n is 2 or 3.

4. The double-layer polyelectrolyte membrane according to claim 2 or 3, wherein the PFSA is a polymer comprising about 900 to about 1100 repeating units represented by structural formula (I).

5. The double-layer polyelectrolyte membrane according to any one of claims 1 to 4, wherein the cross-linked polysulfonated polymer comprises a cross-linking portion represented by one of the following structural formulas: in R 1 , R 2 , R 3 and R 4 Each of which is independently selected from H, C 1-12 Alkyl, C 1-12 Haloalkyl, C 6-14 Aryl and C 6-14 Aryl (C 1-12 Alkylene); R 5 is H or -SO3H, M 2+ Selected from Mr. 2+ , Ca 2+ , Ba 2+ and Al(X) 2+ , wherein X is a halogen, acetate or nitrate; k is 1, 2, 3, or 4, and represents the point of attachment of the cross-linking moiety to the repeating unit of the cross-linked polysulfonated polymer.

6. The double-layer polyelectrolyte membrane according to claim 5, wherein the cross-linked portion is represented by one of the following structural formulas:

7. The double-layer polyelectrolyte membrane according to claim 5, wherein the cross-linked portion is represented by one of the following structural formulas:

8. The double-layer polyelectrolyte membrane according to claim 5, wherein the cross-linked portion is represented by one of the following structural formulas:

9. The double-layer polyelectrolyte membrane according to claim 5, wherein the cross-linked portion is represented by one of the following structural formulas:

10. The double-layer polyelectrolyte membrane according to claim 5, wherein the cross-linked portion is represented by the following structural formula:

11. The double-layer polyelectrolyte membrane according to claim 5, wherein the cross-linked polysulfonated polymer comprises sPPS or sPSU, and the cross-linked portion is represented by one of the following structural formulas:

12. The double-layer polyelectrolyte membrane according to claim 5, wherein the cross-linked polysulfonated polymer comprises sPPS, and the cross-linked portion is represented by one of the following structural formulas:

13. The double-layer polyelectrolyte membrane according to claim 5, wherein the cross-linked polysulfonated polymer comprises sPPS, and the cross-linked portion is represented by the following structural formula:

14. The double-layer polyelectrolyte membrane according to claim 5, wherein the cross-linked polysulfonated polymer comprises sPPS, and the cross-linked portion is represented by one of the following structural formulas:

15. A double-layer polyelectrolyte membrane according to any one of claims 1-10, wherein it comprises a cross-linked polysulfonated polymer, wherein the cross-linked polysulfonated polymer comprises sulfonated polyphenylsulfone (sPPS), sulfonated polyetheretherketone (sPEEK), sulfonated polyphosphazene (sPOP), sulfonated polybenzimidazole (sPBI), sulfonated polyethersulfone (sPES), sulfonated polyaryletherketone (sPAEK), sulfonated polysulfone, sulfonated polysulfide sulfone, sulfonated polyimide (sPI), sulfonated polyetherimide (sPEI), sulfonated polyamine or a combination thereof.

16. The double-layer polyelectrolyte membrane according to claim 15, wherein the cross-linked polysulfonated polymer comprises sPPS, sPEEK, sPOP or sPBI.

17. The double-layer polyelectrolyte membrane of claim 15, wherein the cross-linked polysulfonated polymer comprises sPPS.

18. The double-layer polyelectrolyte membrane of any one of claims 1 to 17, wherein the first layer further comprises a porous matrix, the porous matrix comprising a matrix polymer, and wherein the PFSA and the matrix polymer form an interpenetrating network.

19. The double-layer polyelectrolyte membrane of claim 18, wherein the first layer comprises about 70 wt% to about 99 wt% PFSA.

20. The bilayer polyelectrolyte membrane of claim 18, wherein the first layer comprises about 78 wt% to about 95 wt% PFSA.

21. The double-layer polyelectrolyte membrane according to any one of claims 18 to 20, wherein the matrix polymer is polytetrafluoroethylene (PTFE).

22. The double-layer polyelectrolyte membrane of claim 21, wherein the matrix polymer is expanded polytetrafluoroethylene (ePTFE).

23. The double-layer polyelectrolyte membrane of any one of claims 1-22, wherein the cross-linked polysulfonated polymer has a degree of sulfonation of about 20% to about 100%.

24. The bilayer polyelectrolyte membrane of claim 23, wherein the cross-linked polysulfonated polymer has a degree of sulfonation of about 40% to about 80%.

25. The bilayer polyelectrolyte membrane of claim 23, wherein the cross-linked polysulfonated polymer has a degree of sulfonation of about 50% to about 60%.

26. The double-layer polyelectrolyte membrane of any one of claims 1-22, wherein the cross-linked polysulfonated polymer has a degree of sulfonation of about 100% to about 300%.

27. The bilayer polyelectrolyte membrane of claim 26, wherein the degree of sulfonation of the cross-linked polysulfonated polymer is about 200%.

28. The bilayer polyelectrolyte membrane of any one of claims 1-22, wherein the cross-linked polysulfonated polymer comprises an average of from about 1 to about 3 total sulfonic acid, sulfonate, and sulfonamide groups per repeat unit.

29. The bilayer polyelectrolyte membrane of claim 28, wherein the cross-linked polysulfonated polymer comprises an average of about 2 total sulfonic acid, sulfonate, and sulfonamide groups per repeating unit.

30. The bilayer polyelectrolyte membrane of any one of claims 1-29, wherein the cross-linked polysulfonated polymer has a gel fraction of about 50% to about 100%.

31. The bilayer polyelectrolyte membrane of any one of claims 1-29, wherein the cross-linked polysulfonated polymer has a degree of cross-linking of about 10% to about 95%.

32. The double-layer polyelectrolyte membrane of any one of claims 1-29, wherein the cross-linked polysulfonated polymer has a degree of cross-linking of about 40%.

33. The double-layer polyelectrolyte membrane of any one of claims 1-32, wherein the thickness of the first layer is from about 5 μm to about 175 μm.

34. The double-layer polyelectrolyte membrane of claim 33, wherein the first layer has a thickness of about 25 μm.

35. The double-layer polyelectrolyte membrane of any one of claims 1-34, wherein the thickness of the second layer is from about 0.2 μm to about 170 μm.

36. The double-layer polyelectrolyte membrane of claim 35, wherein the second layer has a thickness of about 0.2 μm to about 10 μm.

37. The double-layer polyelectrolyte membrane of claim 36, wherein the second layer has a thickness of about 0.5 μm to about 2 μm.

38. A double-layer polyelectrolyte membrane according to any one of claims 1-37, wherein the first layer is continuous.

39. A double-layer polyelectrolyte membrane according to any one of claims 1 to 38, wherein the membrane is unsupported.

40. A double-layer polyelectrolyte membrane according to any one of claims 1-16 and 18-39, wherein: The membrane is unsupported, The cross-linked polysulfonated polymer is sPPS, and The cross-linking portion is represented by the following structural formula:

41. The double-layer polyelectrolyte membrane according to claim 8, wherein: The membrane is unsupported, The cross-linked polysulfonated polymer is sPPS, and The cross-linking moiety is represented by one of the following structural formulas:

42. The double-layer polyelectrolyte membrane of claim 5, wherein: The PFSA is a polymer comprising repeating units represented by structural formula (I): in x is an integer between 5 and 14, m is 1 or 2, and n is 2 or 3; and The cross-linked polysulfonated polymer comprises sPPS or sPSU, and the cross-linked portion is represented by one of the following structural formulas:

43. The double-layer polyelectrolyte membrane according to claim 5, wherein: The PFSA is a polymer comprising repeating units represented by structural formula (I): in x is an integer between 5 and 14, m is 1 or 2, and n is 2 or 3; and The cross-linked polysulfonated polymer comprises sPPS, and the cross-linked portion is represented by one of the following structural formulas:

44. The double-layer polyelectrolyte membrane according to claim 5, wherein: The membrane is unsupported, The PFSA is a polymer comprising repeating units represented by structural formula (I): in x is an integer between 5 and 14, m is 1 or 2, and n is 2 or 3; and further wherein The cross-linked polysulfonated polymer is sPPS, The cross-linking portion is represented by the following structural formula: The sulfonation degree of the sPPS is about 200%. The degree of crosslinking of the sPPS is about 40%, and The second layer has a thickness of about 0.5 μm to about 2 μm.

45. The double-layer polyelectrolyte membrane according to claim 5, wherein: The membrane is unsupported, The PFSA is a polymer comprising repeating units represented by structural formula (I): in x is an integer between 5 and 14, m is 1 or 2, and n is 2 or 3; and further wherein The cross-linked polysulfonated polymer is sPPS, The cross-linking moiety is represented by one of the following structural formulas: The sulfonation degree of the sPPS is about 200%. The sPPS has a cross-linking degree of about 25% to about 30%, and The second layer has a thickness of about 1 μm to about 2 μm.

46. ​​A double-layer polyelectrolyte membrane according to any one of claims 5 to 42, wherein: The first layer comprises a porous matrix comprising a matrix polymer, The PFSA and the matrix polymer form an interpenetrating network, and The cross-linked polysulfonated polymer is sPPS.

47. The double-layer polyelectrolyte membrane of claim 46, wherein the cross-linked portion is represented by one of the following structural formulas:

48. The double-layer polyelectrolyte membrane of claim 5, wherein: The first layer comprises a porous matrix, the porous matrix comprising a matrix polymer, and wherein the PFSA and the matrix polymer form an interpenetrating network; The PFSA is a polymer comprising repeating units represented by structural formula (I): in x is an integer between 5 and 14, m is 1 or 2, and n is 2 or 3; The matrix polymer comprises ePTFE; and The cross-linked polysulfonated polymer comprises sPPS, and the cross-linked portion is represented by one of the following structural formulas:

49. A method for manufacturing a double-layer polyelectrolyte membrane according to any one of claims 1 to 48, the method comprising: a) providing a first layer having a first side, and a solution or suspension comprising a polysulfonated polymer and a cross-linking agent, b) coating said first side of said first layer with said solution or suspension, thereby producing a coated first layer; c) exposing the coated first layer to conditions sufficient to cause a cross-linking reaction between the polysulfonated polymer and the cross-linking agent, thereby producing the bilayer polyelectrolyte membrane.

50. The method of claim 49, wherein the cross-linking agent is selected from a polyol, an amine, an epoxide, a thiol, or a compound containing a terminal olefin or alkyne.

51. The method of claim 49, wherein the cross-linking agent is selected from the group consisting of glycerol, ethylene glycol, hydroquinone, 2,5-dihydroxybenzenesulfonic acid, 2,5-dihydroxybenzene-1,4-disulfonic acid, biphenyl, tetraglycidylbis(p-aminophenyl)methane, phenylenediamine, 4,4'-thiobisbenzenethiol, and tetrafluorostyrene.

52. The method of claim 49, wherein the cross-linking agent is selected from the group consisting of glycerol, ethylene glycol, tetraglycidylbis(p-aminophenyl)methane, phenylenediamine, 4,4'-thiobisbenzenethiol, and tetrafluorostyrene.

53. The method of claim 49, wherein the cross-linking agent is a polyol.

54. The method of claim 49, wherein the cross-linking agent is ethylene glycol or glycerol.

55. The method of claim 49, wherein the cross-linking agent is hydroquinone or 2,5-dihydroxybenzenesulfonic acid.

56. The method of any one of claims 49-55, wherein the conditions sufficient to cause the polysulfonated polymer and the cross-linking agent to undergo a cross-linking reaction comprise heating the coated first layer to a cross-linking temperature of about 150°C to about 200°C for a cross-linking time of about 2 hours to about 96 hours.

57. The method of claim 56, wherein the cross-linking temperature is about 180°C.

58. The method of claim 56, wherein the cross-linking time is about 4 hours.

59. The method of any one of claims 49-58, wherein coating the first side of the first layer with the first solution or suspension comprises spraying the first side of the first layer with the first solution or suspension.

60. A membrane electrode assembly (MEA), comprising: A double-layer polyelectrolyte membrane according to any one of claims 1 to 48; cathode; and anode, The double-layer electrolyte membrane is disposed between the anode and the cathode.

61. The MEA of claim 60, wherein the cathode is disposed on the first layer of the double-layer electrolyte membrane, and the anode is disposed on the second layer of the double-layer electrolyte membrane.

62. The MEA of claim 60, wherein the anode is disposed on the first layer of the double-layer electrolyte membrane, and the cathode is disposed on the second layer of the double-layer electrolyte membrane.

63. A fuel cell comprising one or more MEAs according to any one of claims 60 to 62 and one or more airflow bipolar plates.

Citation Information

Cited By

  • Preparation method and application of high-ionic-conductivity composite electrolyte

    CN121123413A

  • Preparation method and application of high ionic conductivity composite electrolyte

    CN121123413B